Spindle-shaped carbon fiber-containing aggregate and method for producing the same, and carbon fiber-reinforced thermoplastic resin particle containing recycled carbon fiber and method for producing the same
Patent Information
- Application Number
- CN202280025751.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-28
- Filing Date
- 2022-03-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-03-28
AI Technical Summary
[0136]根据本公开所涉及的发明1,可提供显示改善的进料性的碳纤维集合体。
Smart Images

Figure CN117136127B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a spindle-shaped carbon fiber-containing assembly and a method for manufacturing the same (“Invention 1”). In particular, this disclosure relates to a feedable spindle-shaped carbon fiber assembly made from recycled carbon fiber (recycled carbon fiber) and a method for manufacturing the same (“Invention 1a”).
[0002] In addition, this disclosure relates to spindle-shaped assemblies of thermoplastic resin fibers and carbon fibers, and methods for manufacturing the same (“Invention 1b”).
[0003] In addition, this disclosure also relates to carbon fiber reinforced thermoplastic resin particles containing recycled carbon fibers manufactured using waste materials from carbon fiber reinforced resin moldings (“Invention 2”). Background Technology
[0004] (Regarding Invention 1, Invention 1a, and Invention 1b)
[0005] Carbon fiber is used as a reinforcing fiber for thermosetting and thermoplastic resins (especially thermoplastic resins) due to its excellent specific strength / specific modulus of elasticity and its lightweight properties. Carbon fiber reinforced resin composites (or carbon fiber reinforced plastics, CFRP) are used not only in sports / general industrial applications, but also in aerospace, automotive, and other wide-ranging applications.
[0006] Regarding carbon fiber, which is used as a raw material for carbon fiber-containing products such as carbon fiber reinforced resin composites, a method for manufacturing granular carbon fiber assemblies from carbon fiber and a bridging agent was discussed. Compared to using carbon fiber directly, this carbon fiber assembly exhibits better feedability when manufacturing carbon fiber-containing products through processes such as extrusion molding.
[0007] Patent document 1 describes a method for manufacturing carbon fiber particles by contacting an aggregate of carbon fibers bundled by a bundling agent with an inclined rotating surface.
[0008] In recent years, there has been an increasing demand for recycled carbon fiber (recycled carbon fiber) recovered from used carbon fiber-containing products. Methods for granulating carbon fiber assemblies have also been explored for such recycled carbon fiber.
[0009] Patent document 2 describes a method for producing carbon fiber particles from recycled carbon fiber using a mixer with an inclined rotating container.
[0010] Patent documents 3 and 4 describe a method for manufacturing cylindrical carbon fiber assemblies from recycled carbon fibers by wet extrusion granulation.
[0011] (Regarding Invention 2)
[0012] One method for producing carbon fiber reinforced resin composites is through carbon fiber reinforced thermoplastic resin particles. These particles come in two types: long-fiber reinforced particles, which are manufactured by coating continuous carbon fibers with thermoplastic resin and then cutting the resulting resin strands; and short-fiber reinforced particles, which are manufactured by mixing and dispersing discontinuous carbon fibers in thermoplastic resin and then cutting the resulting resin strands. Although short-fiber reinforced thermoplastic resin particles have inferior mechanical properties compared to long-fiber reinforced thermoplastic resin particles, they are widely used as a cost-effective manufacturing method.
[0013] Patent documents 5 and 6 describe a method for manufacturing a composite containing recycled carbon fibers by melt blending carbon fibers. The carbon fibers used in this method have residual carbon adhering to them, which is recovered from waste materials of carbon fiber reinforced resin composites and carbonized from the matrix components using a thermal decomposition method.
[0014] Patent document 7 describes a carbon fiber assembly in which a fiber treatment agent is added to recycled carbon fibers recovered from carbon fiber reinforced composite materials, and the carbon fiber is formed into a cylindrical shape using an extrusion granulation machine, thereby improving feedability.
[0015] Existing technical documents
[0016] Patent documents
[0017] Patent Document 1: Japanese Patent No. 3452363;
[0018] Patent Document 2: Description of European Patent Application Publication No. 2902433;
[0019] Patent Document 3: Japanese Patent Application Publication No. 2020-180421;
[0020] Patent document 4: Japanese Patent Application Publication No. 2020-196882;
[0021] Patent Document 5: Japanese Patent Application Publication No. 2020-49820;
[0022] Patent document 6: Japanese Patent Application Publication No. 2019-155634;
[0023] Patent document 7: Japanese Patent Application Publication No. 2021-55198. Summary of the Invention
[0024] The problem that the invention aims to solve (Regarding Invention 1)
[0025] Existing carbon fiber assemblies sometimes have insufficient feedability.
[0026] The object of the invention 1 disclosed herein is to provide a carbon fiber assembly exhibiting improved feedability.
[0027] (Regarding Invention 1a)
[0028] Existing carbon fiber assemblies made using recycled carbon fiber sometimes have insufficient feedability.
[0029] The object of the invention 1a disclosed herein is to provide a carbon fiber assembly containing recycled carbon fiber and exhibiting improved feedability.
[0030] (Regarding Invention 1b)
[0031] Typically, when manufacturing carbon fiber molded articles using the carbon fiber aggregate described above, in addition to the carbon fiber aggregate (primary intermediate material), thermoplastic resin is fed to a mixing mill or the like for mixing to produce granules containing carbon fiber and thermoplastic resin (secondary intermediate material). These granules are then fed to an injection molding machine or the like to manufacture carbon fiber molded articles.
[0032] However, carbon fibers sometimes break during the manufacturing of the secondary intermediate materials. Additionally, if thermoplastic resin can be added to the carbon fiber assembly beforehand, the mixing process for manufacturing the secondary intermediate materials can be omitted, allowing for direct molding of the carbon fiber and thermoplastic resin assembly. However, maintaining the workability of the assembly while incorporating thermoplastic resin into the carbon fiber assembly is not easy.
[0033] The purpose of the invention 1b disclosed herein is to provide an assembly of carbon fiber and thermoplastic resin that is highly operable and can be directly used to manufacture carbon fiber molded articles, and a method thereof.
[0034] (Regarding Invention 2)
[0035] Methods for decomposing used carbon fiber reinforced resin composites and obtaining recycled carbon fibers include: thermal decomposition of resin components by heat treatment (thermal decomposition method), solvent dissolution and removal, and electrolysis. Among the previously widely used methods, thermal decomposition can be listed as an example.
[0036] When using existing recycled carbon fibers obtained through heat treatment and decomposition to manufacture short fiber reinforced thermoplastic resin particles, it is difficult to achieve sufficient reinforcing properties.
[0037] The object of the invention 2 disclosed herein is to provide recycled carbon fiber reinforced thermoplastic resin particles that can be used to manufacture molded articles with excellent mechanical strength, using recycled carbon fiber obtained by a method of decomposition through heat treatment as raw material.
[0038] Means for solving the problem (Regarding Invention 1)
[0039] The above-mentioned problems related to Invention 1 can be solved by the following solution according to Invention 1 of this disclosure:
[0040] <Option 1>
[0041] A method for manufacturing a spindle-shaped assembly, the method comprising:
[0042] Provide a mixture consisting of at least carbon fiber and a binder liquid;
[0043] A spindle-shaped precursor is produced by rotating the above mixture in a container; and
[0044] The above-mentioned precursors were dried.
[0045] <Option 2>
[0046] A spindle-shaped assembly containing carbon fibers and adhesives.
[0047] (Regarding Invention 1a)
[0048] The above-mentioned problems related to invention 1a can be solved by the following solutions A1 to A13 as disclosed in invention 1a:
[0049] <Option A1>
[0050] A method for manufacturing a spindle-shaped carbon fiber assembly, characterized by comprising:
[0051] Provide a mixture consisting of at least recycled carbon fiber and a binder liquid;
[0052] A spindle-shaped precursor is manufactured by rotating the mixture within a container, in the gap between the inner wall of the container and the rotating body within the container; and
[0053] Dry the above-mentioned precursors.
[0054] The aforementioned recycled carbon fiber contains residual carbon components, the content of which, relative to the aforementioned recycled carbon fiber, exceeds 0% by weight and is less than 5.0% by weight; and
[0055] The average length of the aforementioned recycled carbon fibers is greater than 1 mm and less than 30 mm.
[0056] <Option A2>
[0057] The method described in Scheme A1, wherein the average length of the carbon fiber assembly is 1.5 mm to 60 mm.
[0058] <Option A3>
[0059] The method of scheme A1 or A2, wherein the amount of the adhesive-containing liquid in the mixture is 20% to 60% by weight relative to the mixture.
[0060] <Option A4>
[0061] The method according to any one of schemes A1 to A3, wherein the amount of adhesive contained in the adhesive-containing liquid is 0.1 to 10 wt% relative to the above-mentioned recycled carbon fiber.
[0062] <Option A5>
[0063] The method according to any one of schemes A1 to A4 includes: decomposing the plastic components contained in the carbon fiber-containing plastic product by semiconductor thermal activation method to produce the above-mentioned recycled carbon fiber.
[0064] <Option A6>
[0065] The method according to any one of schemes A1 to A5, wherein the average length of the carbon fiber assembly is 1.2 to 4.0 times the average length of the recycled carbon fiber contained in the carbon fiber assembly.
[0066] <Option A7>
[0067] The method according to any one of schemes A1 to A6, wherein the rotating body is a stirring blade.
[0068] <Option A8>
[0069] The method of any one of schemes A1 to A7, wherein the aforementioned precursor is manufactured in a non-tilted container.
[0070] <Option A9>
[0071] A spindle-shaped carbon fiber assembly, characterized in that: it is a carbon fiber assembly composed of at least recycled carbon fibers and an adhesive.
[0072] The average length of the aforementioned recycled carbon fibers is greater than 1 mm and less than 30 mm; and
[0073] The average length of the aforementioned carbon fiber assemblies ranges from 1.5 mm to 60 mm.
[0074] <Option A10>
[0075] The carbon fiber assembly described in Scheme A9, wherein the average length of the spindle-shaped carbon fiber assembly in the long axis direction is 1.2 to 4.0 times the average length of the recycled carbon fiber contained in the spindle-shaped carbon fiber assembly.
[0076] <Option A11>
[0077] The carbon fiber assembly described in scheme A9 or A10, wherein the recycled carbon fibers contained in the spindle-shaped carbon fiber assembly are oriented along the long axis of the spindle-shaped carbon fiber assembly.
[0078] <Option A12>
[0079] The carbon fiber assembly according to any one of schemes A9 to A11, wherein the content of the adhesive is 0.1 to 10 wt% relative to the spindle-shaped carbon fiber assembly.
[0080] <Option A13>
[0081] The carbon fiber assembly according to any one of schemes A9 to A12, wherein the recycled carbon fiber contains residual carbon components.
[0082] Compared to the above-mentioned recycled carbon fiber, the content of the above-mentioned residual carbon component is more than 0% by weight and less than 5.0% by weight.
[0083] (Regarding Invention 1b)
[0084] The aforementioned problems related to invention 1b can be solved by the following solutions B1 to B14 as disclosed in invention 1b:
[0085] <Option B1>
[0086] An aggregate, which is a spindle-shaped assembly of thermoplastic resin fibers and carbon fibers, comprising carbon fibers, thermoplastic resin fibers, and adhesives.
[0087] The carbon fibers and thermoplastic resin fibers contained in the above-mentioned assembly are oriented along the long axis of the above-mentioned assembly.
[0088] <Option B2>
[0089] The assembly described in Scheme B1, wherein the average length of the assembly is 1.5mm to 60mm.
[0090] <Option B3>
[0091] The assembly described in scheme B1 or B2, wherein the average length of the carbon fiber and the thermoplastic resin fiber is 1 mm or more and less than 30 mm.
[0092] <Option B4>
[0093] The assembly according to any one of schemes B1 to B3, wherein the average length of the assembly is 1.2 to 5.0 times the average length of the carbon fibers and the average length of the thermoplastic resin fibers contained in the assembly.
[0094] <Option B5>
[0095] The assembly according to any one of schemes B1 to B4, wherein the content of the adhesive is 0.1% to 10% by weight relative to the assembly.
[0096] <Option B6>
[0097] The assembly of any one of schemes B1 to B5, wherein the thermoplastic resin fiber is selected from polyolefin resin fiber, polyester resin fiber, polyamide resin fiber, polyetherketone resin fiber, polycarbonate resin fiber, phenoxy resin fiber and polyphenylene sulfide resin fiber, and mixtures thereof.
[0098] <Option B7>
[0099] The assembly of any one of schemes B1 to B6, wherein the carbon fiber comprises recycled carbon fiber.
[0100] <Solution B8>
[0101] The assembly according to any one of schemes B1 to B7, wherein the carbon fiber is recycled carbon fiber.
[0102] <Option B9>
[0103] The assembly described in scheme B7 or B8, wherein the recycled carbon fiber contains a residual carbon component, wherein the residual carbon component is more than 0% by weight and less than 5.0% by weight relative to the recycled carbon fiber.
[0104] <Option B10>
[0105] A method for manufacturing an assembly according to any one of schemes B1 to B9, comprising:
[0106] Provide a mixture consisting of at least carbon fiber, thermoplastic resin fiber and a binder liquid;
[0107] A spindle-shaped precursor is produced by rotating the above mixture in a container; and
[0108] The above-mentioned precursors were dried.
[0109] <Option B11>
[0110] The method of scheme B10, wherein a spindle-shaped precursor is produced by rotating the mixture in a container within a gap between the inner wall of the container and a rotating body within the container.
[0111] <Option B12>
[0112] The method described in scheme B10 or B11, wherein the carbon fiber comprises recycled carbon fiber.
[0113] <Option B13>
[0114] The method described in scheme B12, wherein the carbon fiber is recycled carbon fiber.
[0115] <Option B14>
[0116] The method described in scheme B12 or B13 includes: decomposing the plastic components contained in the carbon fiber-containing plastic product by semiconductor thermal activation to produce the above-mentioned recycled carbon fiber.
[0117] (Regarding Invention 2)
[0118] The above-mentioned problems related to Invention 2 can be solved by the following solutions C1 to C7 as disclosed in Invention 2:
[0119] <Option C1>
[0120] Carbon fiber reinforced thermoplastic resin granules, characterized in that: they are carbon fiber reinforced thermoplastic resin granules comprising recycled carbon fibers and thermoplastic resin.
[0121] The aforementioned recycled carbon fibers possess a single-fiber tensile strength of 3.0 GPa or higher and a Weibull shape factor of 6.0 or higher; and
[0122] The aforementioned recycled carbon fiber contains residual carbon components, and the content of the residual carbon components is more than 0% by weight and less than 5.0% by weight relative to the aforementioned recycled carbon fiber.
[0123] <Option C2>
[0124] The carbon fiber reinforced thermoplastic resin particles of Scheme C1, wherein the content of the recycled carbon fiber is 5% by weight or more and 30% by weight or less, relative to the carbon fiber reinforced thermoplastic resin particles.
[0125] <Option C3>
[0126] The carbon fiber reinforced thermoplastic resin particles described in scheme C1 or C2, wherein the thermoplastic resin is selected from polyolefin resins, polyester resins, polyamide resins, polyetherketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins, and mixtures thereof.
[0127] <Option C4>
[0128] The carbon fiber reinforced thermoplastic resin particles in any one of schemes C1 to C3 have a length of 3 mm or more and 10 mm or less in the long side direction.
[0129] <Option C5>
[0130] The carbon fiber reinforced thermoplastic resin particles according to any one of schemes C1 to C4 are characterized in that: the residual average fiber length of the recycled carbon fiber contained in the carbon fiber reinforced thermoplastic resin particles is 300 μm or more.
[0131] <Solution C6>
[0132] The carbon fiber reinforced thermoplastic resin particles according to any one of schemes C1 to C5 are characterized in that they are used to manufacture molded articles with a tensile strength of 90 MPa or more, a flexural strength of 140 MPa or more, and a flexural modulus of elasticity of 7100 MPa or more.
[0133] <Solution C7>
[0134] The carbon fiber reinforced thermoplastic resin particles according to any one of schemes C1 to C6 are characterized in that: the frequency of occurrence of single fibers with a diameter of 300 μm or less in the above-mentioned recycled carbon fibers in the carbon fiber reinforced thermoplastic resin particles is 40% or less.
[0135] Effects of the invention (Regarding Invention 1)
[0136] According to the invention 1 disclosed herein, a carbon fiber assembly exhibiting improved feedability can be provided.
[0137] (Regarding Invention 1a)
[0138] According to the invention 1a disclosed herein, a carbon fiber assembly containing recycled carbon fiber and exhibiting improved feedability can be provided.
[0139] (Regarding Invention 1b)
[0140] According to the invention 1b disclosed herein, an assembly of carbon fiber and thermoplastic resin, which is highly operable and can be directly used to manufacture carbon fiber molded articles, and a method thereof are provided.
[0141] (Regarding Invention 2)
[0142] According to the invention 2 disclosed herein, recycled carbon fiber reinforced thermoplastic resin particles that can be used to manufacture molded articles with excellent mechanical properties can be provided using recycled carbon fiber obtained by a method of decomposition through heat treatment as raw material.
[0143] In particular, the carbon fiber reinforced thermoplastic resin particles according to the present disclosure can be used to manufacture molded articles having the same mechanical strength as those made from carbon fiber reinforced thermoplastic resin particles made from virgin carbon fiber (ordinary carbon fiber, not recycled carbon fiber). Attached Figure Description
[0144] [Figure 1 ] Figure 1 This is a schematic diagram of one embodiment of a mixing pellet mill that can be used in this disclosure.
[0145] [ Figure 2 ] Figure 2 This is a conceptual cross-sectional view used to illustrate the decomposition method involved in Invention 2 of this disclosure.
[0146] [ Figure 3 ] Figure 3 This is a schematic cross-sectional schematic diagram showing one embodiment of the decomposition method involved in Invention 2 of this disclosure.
[0147] [ Figure 4 ] Figure 4 This is a photograph of the multiple carbon fiber assemblies involved in Example A1.
[0148] [ Figure 5 ] Figure 5 This is a photograph of a carbon fiber assembly involved in Example A1.
[0149] [ Figure 6 ] Figure 6 This is a photograph of the carbon fiber assembly obtained in Comparative Example A2.
[0150] [ Figure 7 ] Figure 7 These are photographs of the multiple aggregates involved in Example B2.
[0151] [ Figure 8 ] Figure 8 This is a photograph of an assembly involved in Example B2.
[0152] [ Figure 9 ] Figure 9 This is a photograph showing the material obtained as a result of Comparative Example B1.
[0153] [ Figure 10 ] Figure 10 This is a photo of the CFRP board before heat treatment.
[0154] [ Figure 11 ] Figure 11 This is a photograph of the CFRP board after the processing described in Reference Example 4.
[0155] [ Figure 12 ] Figure 12 This is a photograph of the CFRP board after the treatment described in Comparative Example 2. Detailed Implementation
[0156] (Regarding Invention 1)
[0157] The method for manufacturing the spindle-shaped assembly disclosed in Invention 1 includes:
[0158] Provide a mixture consisting of at least carbon fiber and a binder liquid;
[0159] A spindle-shaped precursor is produced by rotating the above mixture in a container; and
[0160] The above-mentioned precursors were dried.
[0161] Furthermore, the invention disclosed herein includes:
[0162] A spindle-shaped assembly containing carbon fibers and adhesives.
[0163] The assembly disclosed in Invention 1 contains carbon fibers and a binder, and has a spindle-shaped form. When the carbon fiber-containing assembly is spindle-shaped, the contact resistance decreases, resulting in improved flow characteristics of the carbon fiber assembly, which is believed to improve feedability. It should be noted that, in this disclosure, "spindle-shaped" refers to a shape that is thicker in the center and gradually tapers towards both ends.
[0164] The present invention 1 relates to a spindle-shaped assembly (a spindle-shaped carbon fiber-containing assembly), particularly a spindle-shaped carbon fiber assembly, or a spindle-shaped assembly of thermoplastic resin fiber and carbon fiber.
[0165] Regarding the aggregates involved in Invention 1, their manufacturing methods, and their constituent elements and specific schemes, refer to the following descriptions of Inventions 1a and 1b.
[0166] (Regarding Invention 1a)
[0167] The method for manufacturing carbon fiber assemblies disclosed in this invention 1a is characterized by including the following steps:
[0168] Provide a mixture consisting of at least recycled carbon fiber and a binder liquid (providing the process);
[0169] A spindle-shaped precursor is produced by rotating a mixture within a container, in the gap between the container's inner wall and a rotating body inside the container; and
[0170] The precursor is dried (drying process).
[0171] The recycled carbon fiber contains residual carbon components, the content of which is greater than 0% by weight and less than 5.0% by weight relative to the recycled carbon fiber; and
[0172] The average length of recycled carbon fiber is greater than 1 mm and less than 30 mm.
[0173] Typically, when molding products containing carbon fiber, a feeder can be used to supply carbon fiber to extruders, etc., and in particular, a metering feeder can be used to supply carbon fiber in a metered manner. A stable supply of carbon fiber is important for the stable and high-precision manufacturing of molded products.
[0174] Feedability, such as that of carbon fiber, can be improved by mixing / granulating carbon fiber with a binding agent to form carbon fiber assemblies with specific shapes. For example, by forming carbon fiber assemblies into spindle-shaped particles with low contact resistance, the flow characteristics of the carbon fiber assemblies are improved, which is believed to improve feedability.
[0175] However, when using recycled carbon fiber as raw material to manufacture such carbon fiber assemblies, it is not easy to obtain a spindle shape with excellent feedability.
[0176] That is, since recycled carbon fibers are usually obtained by thermally decomposing carbon fiber reinforced resin composites, they have a certain amount of residual carbon from the resin material, thus the fibers are more firmly bonded together. This is not to say that they are limited by theory, but under the stress applied by a pellet mill (especially a rotary agitator), it is not easy to break this bond, so the binder liquid cannot penetrate between the fibers. As a result, it is believed that it is impossible to obtain carbon fiber assemblies with a spindle shape.
[0177] In contrast, in the method of Invention 1a disclosed herein, recycled carbon fibers with a residual carbon content of 5% by weight or less are used as the raw material for the carbon fiber assembly. This is not intended to be theoretically limited, but in such recycled carbon fibers, the fibers are weakly bonded (or not bonded) to each other, and therefore it is believed that under stress applied by a pellet mill or the like, a binder-containing liquid can easily penetrate between the fibers. In this case, a spindle-shaped carbon fiber assembly with excellent flow characteristics can be obtained.
[0178] Furthermore, the length of the recycled carbon fiber used as raw material can also affect feedability. Specifically, if the average length of the recycled carbon fiber is too short, it is considered difficult for the fibers to align in one direction, making it difficult to obtain a spindle-shaped carbon fiber assembly. Conversely, if the average length of the recycled carbon fiber is too long, it is considered that the fibers will entangle, making it difficult for the fibers to align uniformly.
[0179] In contrast, in the method of invention 1a disclosed herein, since the average length of the recycled carbon fiber is 1 mm or more and less than 30 mm, it is believed that the uniform orientation of the fiber is promoted.
[0180] As described above, the manufacturing method according to Invention 1a of this disclosure provides a carbon fiber assembly with excellent feedability. The carbon fiber assembly manufactured according to the manufacturing method of Invention 1a of this disclosure has a spindle-shaped particle shape with good flow characteristics, so that, for example, when supplied to a metering feeder, the metering feeder will not be blocked, and a stable metering supply can be performed.
[0181] <Carbon fiber composite>
[0182] The spindle-shaped carbon fiber assembly manufactured according to the method of invention 1a of this disclosure is an assembly consisting of at least recycled carbon fibers and an adhesive. Preferably, the carbon fiber assembly is substantially composed of recycled carbon fibers and an adhesive. In the carbon fiber assembly, the recycled carbon fibers are bonded together by the adhesive.
[0183] The amount of binder in the carbon fiber assembly is preferably 0.1% to 10% by weight, and more particularly 0.5% to 8% by weight or 1% to 6% by weight, relative to the carbon fiber assembly.
[0184] The carbon fiber assembly obtained by the method disclosed in Invention 1a has a spindle-shaped form. The spindle-shaped carbon fiber assembly exhibits good feedability. This is not intended to be theoretically limited, but because the spindle-shaped carbon fiber assembly has lower contact resistance, it is believed that it will not clog the feeder and can flow into the feeder relatively smoothly.
[0185] (Fiber orientation)
[0186] In the carbon fiber assembly obtained by the method disclosed in Invention 1a, the recycled carbon fibers are preferably oriented along the long axis of the spindle. This orientation of the recycled carbon fibers is not necessarily the same as (parallel to) the long axis of the carbon fiber assembly, but is preferably substantially parallel. More specifically, the average extension direction of the recycled carbon fibers has an angle of less than 45°, less than 40°, less than 30°, less than 20°, less than 10°, less than 5°, less than 2°, less than 1°, less than 0.5°, or less than 0.1° relative to the long axis of the carbon fiber assembly. The average extension direction of the recycled carbon fibers is preferably close to 0° relative to the long axis of the carbon fiber assembly, with no particular limitation on the lower limit; for example, it may exceed 0° or exceed 0.01°.
[0187] The average extension direction of the fibers in a carbon fiber assembly can be determined using a digital camera or optical microscope in a cross-section of the carbon fiber assembly parallel to its long axis.
[0188] (Average length)
[0189] The average length of the carbon fiber assembly can be from 1.5 mm to 60 mm. Preferably, the average length of the carbon fiber assembly is 1.8 mm or more, 2 mm or more, 3 mm or more, 4 mm or more, 5 mm or more, 6 mm or more, 7 mm or more, 8 mm or more, 9 mm or more, 10 mm or more, 11 mm or more, or 12 mm or more and / or 50 mm or less, 40 mm or less, 30 mm or less, or 25 mm or less. When the average length of the carbon fiber assembly is within the above range, good feedability can be obtained.
[0190] The average length of a carbon fiber assembly can be calculated by visually measuring the length along the major axis of 50 carbon fiber assemblies using calipers or other methods, or by averaging the measurements in images obtained using a digital camera or optical microscope.
[0191] Preferably, the average length of the carbon fiber assembly is 1.2 to 4.0 times the average length of the recycled carbon fiber.
[0192] Particularly preferably, the average length of the carbon fiber assembly is 1.4 times, 1.5 times, or 1.6 times the average length of the recycled carbon fiber and / or less than 3.5 times or less than 3.0 times. When the average length of the carbon fiber assembly is within the above range, particularly good feedability can be obtained.
[0193] (Average maximum width of the collection)
[0194] The average maximum width of the carbon fiber assembly can be from 0.1 mm to 3.0 mm. Preferably, the average length of the assembly is 0.2 mm or more, 0.3 mm or more, 0.4 mm or more, or 0.5 mm or more and / or 2.5 mm or less, 2.0 mm or less, 1.8 mm or less, or 1.6 mm or less. The average maximum width of the carbon fiber assembly refers to the average of the maximum length (width) in the direction perpendicular to the length direction. When the average maximum width of the carbon fiber assembly is within the above range, good feedability can be obtained.
[0195] The average maximum width of a carbon fiber assembly can be calculated by visually measuring the maximum length along the minor axis of 50 carbon fiber assemblies in an image obtained using calipers or a digital camera or optical microscope, and then averaging the measurements.
[0196] (Aspect Ratio)
[0197] The aspect ratio of the carbon fiber assembly can be 2–150, 2–100, or 2–50. Furthermore, the aspect ratio of the carbon fiber assembly is preferably 2–20, 3–15, or particularly 4–10. When the aspect ratio is within this range (especially the preferred range), carbon fiber assemblies with particularly excellent shape stability and feedability can sometimes be obtained.
[0198] The aspect ratio is the value obtained by dividing the major diameter of a spindle-shaped carbon fiber assembly by its minor diameter, i.e., major diameter / minor diameter. As the elongation increases, the aspect ratio becomes higher.
[0199] The aspect ratio can be obtained by visually measuring the major and minor axes of a carbon fiber assembly using calipers, or by using a digital camera or optical microscope, and then calculating the aspect ratio. It should be noted that the maximum length (width) in the direction perpendicular to the major axis can be taken as the "minor axis".
[0200] <Provide Process>
[0201] In the method disclosed in 1a, a mixture consisting of at least recycled carbon fibers and a binder liquid is provided.
[0202] The amount of binder-containing liquid in the mixture is preferably 20% to 60% by weight, particularly preferably 25% to 55% by weight or 30% to 50% by weight. In this case, the recycled carbon fibers are bundled particularly well due to the liquid contained in the binder. Furthermore, since the amount of liquid contained in the binder is not excessive, the drying load can be reduced. It should be noted that the binder-containing liquid contains a solvent or dispersion medium. Preferably, the content of solvent or dispersion medium (especially water) in the mixture is 20% to 60% by weight, particularly 25% to 55% by weight or 30% to 50% by weight. More preferably, the content of solvent or dispersion medium (especially water) in the mixture is 20% to 45% by weight, 20% to 40% by weight or 20% to 30% by weight. With such a low content of solvent or dispersion medium (especially water), the drying load can be reduced particularly preferably.
[0203] (Recycled carbon fiber)
[0204] Recycled carbon fiber is the raw material for carbon fiber assemblies, comprising carbon fiber components and residual carbon components. Typically, in recycled carbon fiber, the residual carbon components adhere to the surface of the carbon fiber components.
[0205] There is no particular limitation on the recycled carbon fiber; for example, it can be recycled carbon fiber obtained by heat-treating carbon fiber-containing plastic products such as carbon fiber reinforced plastic (CFRP). The recycled carbon fiber can be the recycled carbon fiber described hereinafter with respect to Invention 2.
[0206] Particularly preferred is that the recycled carbon fiber is obtained by a semiconductor thermal activation method. That is, a particularly preferred embodiment of the method involved in this disclosure includes: decomposing the plastic components contained in a carbon fiber-containing plastic product by a semiconductor thermal activation method to produce recycled carbon fiber.
[0207] It should be noted that the "thermal activation of semiconductors" (TASC method) is a method that utilizes the thermal activation of semiconductors (TASC) to decompose polymers and other compounds. For methods of manufacturing recycled carbon fibers by decomposing the plastic components in carbon fiber-containing plastic products using the thermal activation of semiconductors, please refer to, for example, Japanese Patent No. 4517146 and Japanese Unexamined Patent Application Publication No. 2019-189674. For methods of manufacturing recycled carbon fibers using the thermal activation of semiconductors, please refer to the description in Invention 2 of this disclosure, which will be described later.
[0208] (Carbon fiber composition)
[0209] The carbon fiber component in recycled carbon fiber typically originates from carbon fiber contained in carbon fiber-containing products that serve as raw materials for recycled carbon fiber. The carbon fiber component in recycled carbon fiber can be modified through processes such as heat treatment during the manufacturing of recycled carbon fiber.
[0210] The carbon fiber components in recycled carbon fiber can be, for example, PAN-based carbon fiber or pitch-based carbon fiber.
[0211] There are no particular limitations on the morphology of the carbon fiber components in recycled carbon fiber; it can be a carbon fiber bundle composed of multiple monofilaments (single fibers, filaments). The number of filaments constituting the carbon fiber bundle can range from 1,000 to 80,000 or from 3,000 to 50,000. Furthermore, the diameter of the filaments constituting the carbon fiber components in recycled carbon fiber can be from 0.1 μm to 30 μm, 1 μm to 10 μm, or 3 μm to 8 μm.
[0212] (Residual carbon components)
[0213] The residual carbon component in recycled carbon fiber is particularly derived from the residual carbon in the resin contained in the carbon fiber-containing plastic products used as raw materials in the manufacture of recycled carbon fiber.
[0214] In the method disclosed in Invention 1a, the residual carbon content is more than 0% by weight and less than 5.0% by weight relative to the recycled carbon fiber. In this case, a carbon fiber assembly with improved feedability can be obtained.
[0215] In addition, when the residual carbon content is more than 0% by weight and less than 5.0% by weight, pollution caused by a high carbon content (especially carbon) can be avoided. Furthermore, the carbon content that can become foreign matter when manufacturing carbon fiber-containing products using carbon fiber assemblies as materials can be reduced. In addition, the uniform distribution of fibers in carbon fiber-containing products can be improved.
[0216] Preferably, the residual carbon content is 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less relative to recycled carbon fiber. It is preferable to minimize the residual carbon content as much as possible, which may be 0.1% by weight or more, 0.2% by weight or more, 0.4% by weight or more, 0.6% by weight or more, 0.8% by weight or more, 1.0% by weight or more, or 1.2% by weight or more relative to recycled carbon fiber.
[0217] The residual carbon content in recycled carbon fibers can be measured by thermogravimetric analysis (TGA).
[0218] The measurement of residual carbon composition based on thermogravimetric analysis can be performed in the following order:
[0219] (i) For a sample of 1–4 mg obtained by pulverizing recycled carbon fiber, a thermogravimetric analysis was performed in a thermogravimetric analyzer for a total of 300 minutes at an air supply rate of 0.2 L / min, a heating rate of 5 °C / min, and a recording speed of 1 / 6 second, with the following steps:
[0220] From room temperature to 100°C,
[0221] Keep at 100℃ for 30 minutes.
[0222] Heating from 100℃ to 400℃, and
[0223] Maintain at 400℃;
[0224] (ii) Determine the inflection point of the slope in the curve of weight loss rate versus time, and subtract the weight loss rate during the holding period at 100°C from the weight loss rate value at that inflection point to calculate the residual carbon content.
[0225] It should be noted that if the inflection point of the slope cannot be determined under the above conditions, a total of approximately 600 minutes of thermogravimetric analysis with a holding time of 480 minutes at 400°C can be performed instead of a total of 300 minutes of thermogravimetric analysis. Furthermore, a holding time of 480 minutes at a specific temperature within the range of 400°C to 500°C can be performed instead of holding time at 400°C for 480 minutes.
[0226] In addition, when recycled carbon fibers contain resin through processes such as sizing, the residual carbon content can be measured using the above method after the resin is removed.
[0227] (Average length)
[0228] The recycled carbon fiber has an average length of 1 mm or more and less than 30 mm. Recycled carbon fiber with this length range can be obtained, for example, by cutting recycled carbon fiber with a longer dimension. The average length of the recycled carbon fiber can be 2 mm or more, 3 mm or more, or 4 mm or more, and / or less than 29 mm, 28 mm or less, 27 mm or less, 26 mm or less, 25 mm or less, 24 mm or less, 23 mm or less, 22 mm or less, 21 mm or less, 20 mm or less, 15 mm or less, or 10 mm or less. In particular, the average length of the recycled carbon fiber can be 8 mm to 25 mm or 9 mm to 20 mm.
[0229] In the preferred embodiment of invention 1a disclosed herein, the average length of the recycled carbon fiber is 2 mm or more and 20 mm or less, particularly 3 mm or more and 15 mm or less. In this case, particularly good feedability can be obtained.
[0230] Furthermore, in one embodiment of invention 1a disclosed herein, the average length of the recycled carbon fibers is greater than 6 mm and less than 30 mm, particularly greater than 8 mm and less than 25 mm. In this case, when manufacturing carbon fiber-containing products using carbon fiber assemblies, carbon fiber-containing products with particularly excellent physical properties such as strength can sometimes be obtained.
[0231] The average length of recycled carbon fiber can be calculated by visually measuring the length of 50 recycled carbon fibers in an image obtained using a digital camera or optical microscope, and then averaging the measured values.
[0232] (Contains adhesive liquid)
[0233] A binder-containing liquid is a binder dispersion or binder solution containing binder and solvent or dispersion medium.
[0234] (Adhesive)
[0235] The adhesive serves to bundle the recycled carbon fibers within the carbon fiber assembly and maintain the shape of the carbon fiber assembly. There are no particular limitations on the adhesive, but thermoplastic or thermosetting resins are preferred. More specifically, examples of adhesives include: epoxy resins, urethane-modified epoxy resins, polyester resins, phenolic resins, polyamide resins, polyurethane resins, polycarbonate resins, polyetherimide resins, polyamide-imide resins, polyimide resins, bismaleimide resins, polysulfone resins, polyethersulfone resins, epoxy-modified urethane resins, polyvinyl alcohol resins, and polyvinylpyrrolidone resins. These resins can be used alone or in combination of two or more.
[0236] In addition, other adhesives include: bentonite, lignosulfonate, molasses, carboxymethyl cellulose, konjac starch, sodium alginate, polyacrylamide, polyvinyl acetate, polyvinyl alcohol, and starch. These can be used alone or in combination of two or more, and can also be used in conjunction with the aforementioned resins.
[0237] (Solvent, dispersion medium)
[0238] There are no particular limitations on the solvent or dispersion medium, as long as it is a liquid capable of dissolving or dispersing the adhesive. Examples of solvents or dispersion media include: water, alcohols (e.g., methanol or ethanol), ketones (e.g., butanone or acetone), hydrocarbons (e.g., cyclohexane, toluene, or xylene), halogenated hydrocarbons (e.g., dichloromethane), amides (e.g., N-methylpyrrolidone or dimethylformamide), and ethers (e.g., tetrahydrofuran). Water is particularly preferred as the solvent or dispersion medium.
[0239] The binder-containing liquid used in this disclosure can be prepared, for example, by further adding a solvent or dispersion medium to a commercially available sizing agent of high concentration consisting of a binder and a solvent or dispersion medium. In particular, the binder-containing liquid can be prepared by adding a dispersion medium (especially water) to a sizing agent having a binder and a dispersion medium (especially water).
[0240] The sizing agent (and the adhesive-containing liquid obtained by adding a solvent or dispersion medium to the sizing agent) can be, for example, in the form of an aqueous emulsion in which the adhesive is dispersed in water, and in particular, can be an aqueous polyurethane.
[0241] There is no particular limitation on the concentration of the binder in the sizing agent; for example, it can be 10–80% by weight, 20–60% by weight, or 30–50% by weight.
[0242] The amount of adhesive relative to the binder-containing liquid can be 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, or 1.5% by weight or more, and / or 20% by weight or less, 15% by weight or less, 10% by weight or less, 8% by weight or less, or 7% by weight or less. The amount of adhesive relative to the binder-containing liquid is particularly preferably 1% to 10% by weight or 2% to 8% by weight. The amount of solvent or dispersion medium (especially water) relative to the binder-containing liquid can be 80% by weight or more, 85% by weight or more, 90% by weight or more, 92% by weight or more, or 93% by weight or more, and / or 99.9% by weight or less, 99.5% by weight or less, 99% by weight or less, or 98.5% by weight or less.
[0243] In addition, the amount of binder is preferably 0.1% to 10% by weight, particularly preferably 0.5% to 8% by weight, or 1% to 7% by weight, relative to recycled carbon fiber.
[0244] (Fiber Opening)
[0245] Recycled carbon fibers can be pre-treated by splitting them. This splitting process eliminates the entanglement of fibers and can sometimes promote the orientation of fibers in one direction during the pelleting process.
[0246] There are no particular limitations on the method of fiber opening; for example, it can be done by rotating blades. The rotating blades used for fiber opening can be auxiliary blades equipped in a pellet mill.
[0247] Alternatively, fiber opening can also be achieved through high-speed mixing.
[0248] (mix)
[0249] There are no particular limitations on the method for obtaining the mixture from recycled carbon fiber and the binder-containing liquid. The recycled carbon fiber and the binder-containing liquid can be added to a container used in the granulation process in a mixed form. For example, the binder-containing liquid can be injected into a block of recycled carbon fiber, and the mixture can be obtained by random stirring before being added to a container. Alternatively, the recycled carbon fiber and the binder-containing liquid can be added separately to a container and mixed therein to form the mixture. Mixing and granulation can be carried out simultaneously.
[0250] The recycled carbon fibers and binder-containing liquid in the mixture do not necessarily need to be uniformly distributed within the mixture. The mixture can be stirred during the granulation process to improve uniformity.
[0251] <Granulation Process>
[0252] In the method disclosed herein, a spindle-shaped precursor is produced by rotating a mixture in a container within a gap between the inner wall of the container and a rotating body inside the container (hereinafter, this process is sometimes referred to as "granulation process").
[0253] This is not intended to be theoretically limited, but by rotating a mixture containing recycled carbon fibers and a binder-containing liquid within the gap between the inner wall of a container and a rotating body inside the container, the fibers are oriented in a specific direction and bonded together by the binder, resulting in a precursor with a spindle shape.
[0254] There are no particular limitations on the method used to rotate the mixture within the gap between the inner wall of the container and the rotating body inside the container. See below for reference. Figure 1 The example methods used for it are described below.
[0255] Figure 1 This is a schematic diagram of one embodiment of a mixing pellet mill that can be used in this disclosure. Figure 1 The mixing granulator 100 has a cylindrical container section 120 as a container and a mixing blade 140 as a rotating body. Figure 1The mixing granulator 100 is horizontal, and under normal use, the opening of the container section 120 is open to the side. Figure 1 This is a viewpoint observed from inside the container section. A shaft 160 is mounted on the inner wall of the container section 120 opposite the opening (the inner wall from the aforementioned viewpoint). The shaft 160 extends horizontally. The stirring blade 140 is rotatable around this shaft 160 (it should be noted that although in...). Figure 1 In the example, it's counter-clockwise ("A"), but it could also be clockwise. That is, Figure 1 The stirring blades 140 are configured to rotate in a plane parallel to the direction of gravity. It should be noted that, although in Figure 1 Although not shown in the diagram, auxiliary blades for opening the fibers can also be provided inside the container section 120.
[0256] In the granulation process, a mixture containing recycled carbon fibers and a binder-containing liquid is randomly mixed / stirred using a stirring blade 140 rotating within the container section 120, causing the mixture to be stirred between the inner wall of the container section 120 and the stirring blade 140 within the container section 120. Figure 1 (Represented by the symbol "C") Rotates within the gap.
[0257] Granulation can be performed at ambient temperature or by heating. Granulation can be performed for, for example, 1 minute to 1 hour, 5 minutes to 20 minutes, or 8 minutes to 15 minutes.
[0258] (container)
[0259] There are no particular limitations on the container disclosed herein, as long as it can hold the mixture therein and is suitable for performing the granulation process described above. The container is preferably made of a material with excellent rigidity and durability. In particular, the inner wall of the container is preferably made of a material that does not cause wear or the like during the rotation of the mixture, or has undergone a surface treatment for this purpose.
[0260] In one embodiment of this disclosure, the container is not tilted and is substantially parallel to the horizontal direction. For example, the portion of the inner wall of the container that is downward in the direction of gravity is not tilted and can be substantially parallel to the horizontal direction.
[0261] (Solid of Revolution)
[0262] The rotating body is configured such that a mixture containing recycled carbon fiber and a binder-containing liquid can rotate between itself and the inner wall of the container by rotating within the container. The rotating body is, for example, mounted on a shaft provided within the container, and configured to rotate around that shaft.
[0263] The rotating body preferably has the shape of blades (fly blades). The rotating body is particularly preferably agitator blades (agitation fly blades). The agitator blades are preferably made of a material with excellent rigidity and durability, and are particularly preferably made of a material that will not cause wear during the rotation of the mixture, or have undergone surface treatment for this purpose.
[0264] (gap)
[0265] The size of the gap between the inner wall of the container and the rotating body, that is, the distance between the inner wall of the container and the rotating body, can be constant, or a variety of values that are continuous or discontinuous.
[0266] The size of the gap between the inner wall of the container and the rotating body inside the container, i.e. the distance between the inner wall of the container and the rotating body, can be appropriately set according to the desired size of the carbon fiber assembly, for example, it can be 1 to 10 mm.
[0267] (Mixing Granulator)
[0268] As an apparatus having the aforementioned container and rotating body, a known stirred granulator can be used. There are no particular limitations on the stirred granulator; for example, a Henschel type granulator (Henschel mixer), a Bagmill type granulator, or an Eirich type stirred granulator can be used. The stirred granulator can be either vertical or horizontal.
[0269] (Spindle-shaped precursor)
[0270] The spindle-shaped precursor contains recycled carbon fibers and a binder, and also contains a liquid (especially water) from the binder-containing liquid. The liquid (especially water) in the precursor can be removed by the drying process described below.
[0271] <Drying Process>
[0272] In the method disclosed herein, the obtained spindle-shaped precursor is dried.
[0273] There are no particular limitations on the method for drying the precursor; the temperature and time conditions can be appropriately determined based on factors such as the moisture content of the obtained precursor. It should be noted that, to reduce the drying load, the spindle-shaped precursor can be dehydrated after the granulation process and before the drying process.
[0274] Carbon fiber composite
[0275] The present invention 1a includes the following carbon fiber assembly:
[0276] A spindle-shaped carbon fiber assembly, characterized in that: it is a carbon fiber assembly composed of at least recycled carbon fibers and an adhesive.
[0277] Among them, the average length of recycled carbon fiber is greater than 1 mm and less than 30 mm; and
[0278] The average length of the carbon fiber assembly is 1.5 mm to 60 mm.
[0279] This carbon fiber assembly exhibits particularly good feedability due to its shape. There are no particular limitations on the method for manufacturing this carbon fiber assembly. The carbon fiber assembly according to invention 1a of this disclosure can be manufactured, for example, by the method described above. Regarding the constituent elements of this carbon fiber assembly, refer to the above description of the method for manufacturing the carbon fiber assembly.
[0280] <Bulk density>
[0281] The carbon fiber aggregate disclosed herein preferably has a bulk density of 50 g / L or more, 75 g / L or more, or 100 g / L or more, and / or 500 g / L or less, 400 g / L or more, 300 g / L or less, or 200 g / L or less.
[0282] Bulk density can be measured as follows:
[0283] Using a funnel with an outlet inner diameter of 18 mm, the sample was poured from a height of 63 mm into a 200 ml container with an inner diameter of 63 mm, filling it completely. The weight of the chopped sample was then measured. The bulk density was calculated based on this weight and the container's volume.
[0284] (Regarding Invention 1b)
[0285] The spindle-shaped assembly of thermoplastic resin fibers and carbon fibers disclosed in Invention 1b of this invention comprises carbon fibers, thermoplastic resin fibers, and an adhesive.
[0286] The carbon fibers and thermoplastic resin fibers contained in the aggregate are oriented along the long axis of the aggregate.
[0287] The aggregate disclosed in Invention 1b contains thermoplastic resin fibers, i.e., fibrous thermoplastic resin. This is not intended to be a theoretical limitation, but it is believed that because the thermoplastic resin is fibrous, carbon fibers and thermoplastic fibers easily align in a certain direction, resulting in a tendency to aggregate into granular aggregates, which are then spindle-shaped. When the aggregate is granular, the operability is improved when using it to manufacture carbon fiber-containing molded articles. Furthermore, it is believed that the spindle-shaped aggregate has particularly good feedability (supplyability) when using it to manufacture carbon fiber-containing products. This is not intended to be a theoretical limitation, but it is believed that the spindle-shaped aggregate has lower contact resistance, thus preventing blockage of the feed port of extruders, etc., and allowing for smoother flow into the feed port.
[0288] In addition, the aggregate involved in the present invention 1b contains thermoplastic resin fibers in addition to carbon fibers. Therefore, unlike the existing carbon fiber aggregates that only contain carbon fibers, the process of mixing carbon fiber aggregates and thermoplastic resins to manufacture granules can be omitted, and the molding of carbon fiber-containing articles can be directly carried out.
[0289] Furthermore, the assembly according to Invention 1b of this disclosure eliminates the need for the granulation process required in the case of existing carbon fiber assemblies, thus preventing carbon fiber breakage during granulation. Therefore, it is believed that by using the assembly according to this disclosure to manufacture carbon fiber-containing molded articles, molded articles with improved physical properties can be obtained.
[0290] The invention disclosed herein will now be described in further detail.
[0291] <An assembly of thermoplastic resin fibers and carbon fibers>
[0292] The thermoplastic resin fiber and carbon fiber aggregate involved in this invention 1b is spindle-shaped.
[0293] It contains carbon fiber, thermoplastic resin fiber, and adhesive.
[0294] The carbon fibers and thermoplastic resin fibers contained in the aggregate are oriented along the long axis of the aggregate.
[0295] The assembly disclosed in invention 1b comprises carbon fibers, thermoplastic resin fibers, and an adhesive. In the assembly, the fibrous components composed of carbon fibers and thermoplastic resin are bonded together by the adhesive. The assembly is preferably substantially composed of carbon fibers, thermoplastic resin fibers, and an adhesive, and is particularly preferred to be composed of these constituent elements.
[0296] The amount of adhesive in the aggregate is preferably 0.1% to 10% by weight, particularly 0.5% to 9% by weight, or 1% to 8% by weight, relative to the aggregate.
[0297] The aggregate may contain 1 to 1000 parts by weight, 5 to 900 parts by weight, 10 to 750 parts by weight, 20 to 500 parts by weight, or 50 to 250 parts by weight of thermoplastic resin fiber relative to 100 parts by weight of carbon fiber.
[0298] The aggregates involved in this disclosure have a spindle-shaped shape. As mentioned above, a spindle shape refers to a shape that is thicker in the middle and gradually tapers towards both ends.
[0299] (Fiber orientation)
[0300] In the assembly disclosed in Invention 1b, the fibrous components (carbon fibers and thermoplastic resin fibers) contained in the assembly are oriented along the long axis of the spindle shape. It should be noted that when the assembly is a deformed spindle shape (e.g., a curved spindle shape), "fiber orientation along the long axis of the spindle shape" means that the fibers contained in the assembly are oriented along the axis of the deformed spindle-shaped assembly. This fiber orientation does not necessarily need to be the same as (parallel to) the long axis of the assembly; it is preferably substantially parallel. More specifically, the average extension direction of the fibers has an angle of 45° or less, 40° or less, 30° or less, 20° or less, or 10° or less relative to the long axis of the spindle-shaped assembly. The average extension direction of the fibers is preferably close to about 0° relative to the long axis of the spindle-shaped assembly; there is no particular limitation on the lower limit, for example, it can exceed 0°, 1° or more, or 2° or more.
[0301] The average extension direction of the fibers relative to the long axis of the assembly can be determined using a digital camera or optical microscope by calculating the average value of measurements taken from randomly selected fibers (N=30) in a cross-section parallel to the long axis of the assembly. It should be noted that this calculation does not include fuzzy fibers (fibers partially away from the assembly).
[0302] The average extension direction of the fibers relative to the long axis of the assembly can also be roughly determined by using a digital camera or optical microscope, etc., by calculating the average value based on the measurements of randomly selected fibers (N=30) on the surface of the assembly. In this case, fuzzy fibers (fibers partially away from the assembly) are not included.
[0303] It should be noted that when the assembly is a deformed spindle shape (e.g., a curved spindle shape), the fiber orientation and fiber extension direction can be determined relative to the axis of the assembly. The length and aspect ratio of the assembly can also be determined in the same way.
[0304] (Average length of the collection)
[0305] The average length of the assembly involved in Invention 1b of this disclosure can be from 1.5 mm to 60 mm. Preferably, the average length of the assembly is 1.8 mm or more, 2.0 mm or more, 3.0 mm or more, 4.0 mm or more, 5.0 mm or more, 6.0 mm or more, 7.0 mm or more, 8.0 mm or more, 9.0 mm or more, 10 mm or more, 11 mm or more, 12 mm or more, or 15 mm or more, and / or 50 mm or less, 40 mm or less, 30 mm or less, or 25 mm or less. It is believed that when the average length of the assembly is within the above range, particularly good feeding performance can be obtained.
[0306] The average length of the assembly can be calculated by visually measuring the lengths of 50 assemblies along their major axes using calipers or by averaging the measurements from images obtained using a digital camera or optical microscope.
[0307] Preferably, the average length of the assembly is 1.2 to 5.0 times the average length of the carbon fibers and the average length of the thermoplastic resin fibers contained in the assembly. When the average length of the assembly is within the above range, particularly good feedability can sometimes be obtained.
[0308] Particularly preferably, the average length of the assembly is 1.4 times, 1.5 times, or 1.6 times or more, and / or 4.5 times, 4.0 times, 3.5 times, 3.0 times, or 2.5 times or less, of the average length of the carbon fiber and the average length of the thermoplastic resin fiber. When the average length of the assembly is within the above range, particularly good feedability can sometimes be obtained.
[0309] The average length of carbon fiber and the average length of thermoplastic resin fiber can be calculated by visually measuring the length of 50 fibers using calipers or by averaging the measured values in an image obtained using a digital camera or optical microscope.
[0310] (Average maximum width of the collection)
[0311] The average maximum width of the carbon fiber assembly can be from 0.1 mm to 5.0 mm. Preferably, the average length of the assembly is 0.2 mm or more, 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, 1.0 mm or more, 1.5 mm or more, or 2.0 mm or more, and / or 4.5 mm or less or 4.0 mm or less. The average maximum width of the carbon fiber assembly refers to the average of the maximum length (width) in the direction perpendicular to the length direction. When the average maximum width of the carbon fiber assembly is within the above range, good feedability can be obtained.
[0312] The average maximum width of a carbon fiber assembly can be calculated by visually measuring the maximum length along the minor axis of 50 carbon fiber assemblies in an image obtained using calipers or a digital camera or optical microscope, and then averaging the measured values.
[0313] (Aspect Ratio)
[0314] The aspect ratio of the carbon fiber assembly can be 2–150, 2–100, or 2–50. Furthermore, the aspect ratio of the assembly is preferably 2–20, 3–15, or 4–10. When the aspect ratio is within this range (especially this preferred range), assemblies with particularly excellent shape stability and feedability can sometimes be obtained.
[0315] The aspect ratio is the value obtained by dividing the major diameter of a spindle-shaped assembly by its minor diameter, i.e., major diameter / minor diameter. As the elongation increases, the aspect ratio becomes higher.
[0316] The aspect ratio can be obtained by visually measuring the major and minor axes of an assembly using calipers or by using a digital camera or optical microscope, and then calculating the major axis / minor axis ratio. It should be noted that the maximum length (width) in the direction perpendicular to the major axis can be taken as the "minor axis".
[0317] There is no particular limitation on the method of manufacturing the assembly involved in invention 1b of this disclosure. The assembly involved in invention 1b of this disclosure can be manufactured, for example, by the method involved in invention 1b of this disclosure described later.
[0318] <Bulk density>
[0319] The aggregate involved in the present invention 1b preferably has a bulk density of 50 g / L or more, 75 g / L or more, or 100 g / L or more, and / or 500 g / L or less, 400 g / L or less, 300 g / L or less, or 200 g / L or less.
[0320] For the method of measuring bulk density, please refer to the above description of Invention 1a.
[0321] (Carbon fiber)
[0322] Carbon fiber is a raw material for aggregates, including: ordinary carbon fiber (non-recycled carbon fiber, so-called virgin carbon fiber), recycled carbon fiber, and mixtures thereof. Carbon fiber can be, for example, PAN-based carbon fiber or pitch-based carbon fiber.
[0323] There are no particular limitations on the morphology of carbon fibers; they can be in the form of carbon fiber bundles composed of multiple monofilaments (single fibers, filaments). The number of filaments constituting the carbon fiber bundle can range from 1,000 to 80,000, or from 3,000 to 50,000. Furthermore, the diameter of the carbon fiber filaments can range from 0.1 μm to 30 μm, 1 μm to 10 μm, or 3 μm to 8 μm.
[0324] (Recycled carbon fiber)
[0325] Regenerated carbon fiber (recycled carbon fiber) includes carbon fiber components and carbon components other than carbon fiber components (especially residual carbon components). Typically, in recycled carbon fiber, the carbon components other than carbon fiber components are attached to the surface of the carbon fiber components.
[0326] There is no particular limitation on the recycled carbon fiber; for example, it can be recycled carbon fiber obtained by heat-treating carbon fiber-reinforced plastic products such as carbon fiber reinforced plastic (CFRP). The recycled carbon fiber can be the recycled carbon fiber described hereinafter with respect to Invention 2.
[0327] Particularly preferred embodiments of the method disclosed herein include: producing recycled carbon fibers by decomposing the plastic components contained in a carbon fiber-containing plastic product using a semiconductor thermal activation method.
[0328] Regarding the “semiconductor thermal activation method” (TASC method), please refer to the above description of Invention 1a.
[0329] The carbon fiber components in recycled carbon fiber can be modified through heat treatment or other processes during the manufacturing process. For details regarding the carbon fiber components in recycled carbon fiber, please refer to the documentation on carbon fiber mentioned above.
[0330] The residual carbon component in recycled carbon fiber typically originates from the resin contained in the carbon fiber-containing plastic products used as raw materials in the manufacture of recycled carbon fiber. Typically, during the heat treatment of carbon fiber-containing plastic products, the plastic components undergo thermal decomposition, leaving residual carbon on the surface of the carbon fiber components.
[0331] In this disclosure, preferably, the residual carbon content is more than 0% by weight and less than 5.0% by weight relative to the recycled carbon fiber. In this case, an aggregate with improved feedability can sometimes be obtained.
[0332] Furthermore, when the residual carbon content is between 0% and 5.0% by weight, contamination caused by excessive carbon content (especially carbon) can be avoided. Additionally, when manufacturing carbon fiber-containing products using aggregates as materials, the amount of carbon content that could become foreign matter can be reduced. Furthermore, the uniform distribution of fibers in carbon fiber-containing products can be improved.
[0333] Preferably, the residual carbon content is 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less relative to the recycled carbon fiber. It is preferable to minimize the residual carbon content as much as possible, which may be 0.1% by weight or more, 0.2% by weight or more, 0.4% by weight or more, 0.6% by weight or more, 0.8% by weight or more, 1.0% by weight or more, or 1.2% by weight or more relative to the carbon fiber.
[0334] The residual carbon content in recycled carbon fibers can be measured by thermogravimetric analysis (TGA).
[0335] For the method of measuring residual carbon content based on thermogravimetric analysis, please refer to the above description of the invention 1a.
[0336] (Thermoplastic resin fiber)
[0337] Examples of thermoplastic resin fibers include: polyolefin resin fibers (e.g., polypropylene resin fibers and polyethylene resin fibers), polyester resin fibers (e.g., polyethylene terephthalate resin fibers, polybutylene terephthalate resin fibers and polylactic acid resin fibers), polyamide resin fibers, polyetherketone resin fibers, polycarbonate resin fibers, phenoxy resin fibers, and polyphenylene sulfide resin fibers. Thermoplastic resin fibers may be only one type or a mixture of two or more thermoplastic resin fibers.
[0338] (Average fiber length)
[0339] Carbon fibers can have an average length of 1 mm or more and less than 30 mm. Fibers with lengths within this range can be obtained, for example, by cutting fibers with longer dimensions. The average length of carbon fibers can be 2 mm or more, 3 mm or more, or 4 mm or more, and / or can be less than 29 mm, less than 28 mm, less than 27 mm, less than 26 mm, less than 25 mm, less than 24 mm, less than 23 mm, less than 22 mm, less than 21 mm, less than 20 mm, less than 15 mm, or less than 10 mm. In particular, the average length of carbon fibers can be 8 mm to 25 mm, or 9 mm to 20 mm.
[0340] In the preferred embodiment of invention 1b disclosed herein, the average length of the carbon fiber is 2 mm or more and 20 mm or less, particularly 3 mm or more and 15 mm or less. In this case, particularly good feedability can be obtained.
[0341] Furthermore, in one embodiment of invention 1b of this disclosure, the average length of the carbon fiber is greater than 6 mm and less than 30 mm, particularly 8 mm or more and less than 25 mm. In this case, when manufacturing carbon fiber-containing products using the aggregates disclosed herein, carbon fiber-containing products with particularly excellent physical properties such as strength can sometimes be obtained.
[0342] Thermoplastic resin fibers may have an average length of 1 mm or more and less than 30 mm. Fibers with lengths within this range can be obtained, for example, by cutting fibers with longer dimensions. The average length of the thermoplastic resin fibers may be 1.5 mm or more, 2 mm or more, or 3 mm or more, and / or may be less than 28 mm, less than 26 mm, less than 24 mm, less than 22 mm, less than 20 mm, less than 18 mm, less than 16 mm, less than 14 mm, less than 12 mm, less than 10 mm, or less than 8 mm.
[0343] When the average length of carbon fiber and thermoplastic resin fiber is 1 mm or more but less than 30 mm, it is believed that uniform fiber orientation is promoted, resulting in a spindle-shaped assembly with particularly good feedability. This is not intended to be theoretically limited, but it is believed that because the average length of the raw fiber is sufficiently long, the fibers can easily orient themselves in one direction, resulting in a spindle-shaped assembly. Furthermore, because the average fiber length is sufficiently short, fiber entanglement is prevented, which, as a result, promotes uniform fiber orientation.
[0344] The average length of carbon fiber and thermoplastic resin fiber can be calculated by visually measuring the length of 50 fibers using calipers or other methods, or by averaging the measured values in an image obtained using a digital camera or optical microscope.
[0345] Methods for Manufacturing Assemblies
[0346] The present invention 1b includes a method for manufacturing the assembly involved in the present invention 1b, the method comprising the following steps:
[0347] Provide a mixture consisting of at least carbon fiber, thermoplastic resin fiber and a binder liquid (providing the process);
[0348] Spindle-shaped precursors are produced by rotating the mixture in a container (granulation process); and
[0349] Dry the precursor (drying process).
[0350] Regarding the constituent elements involved in the above manufacturing method, please refer to the above description of the assembly involved in the present invention 1b.
[0351] <Provide Process>
[0352] In the method disclosed in Invention 1b, a mixture comprising at least carbon fibers, thermoplastic resin fibers, and a binder-containing liquid is provided. The mixture is particularly composed of carbon fibers, thermoplastic resin fibers, and a binder-containing solution.
[0353] The amount of binder-containing liquid in the mixture is preferably 20% to 70% by weight, particularly preferably 25% to 60% by weight, or 30% to 50% by weight. In this case, the liquid contained in the binder allows for particularly good fiber bundling. Furthermore, since the amount of liquid contained in the binder is not excessive, the drying load can be reduced. It should be noted that the binder-containing liquid contains a solvent or dispersion medium. Preferably, the content of the solvent or dispersion medium (especially water) in the mixture is 20% to 70% by weight, particularly 25% to 60% by weight, or 30% to 50% by weight. More preferably, the content of the solvent or dispersion medium (especially water) in the mixture is 20% to 45% by weight, 20% to 40% by weight, or 20% to 30% by weight. With such a low content of solvent or dispersion medium (especially water), the drying load can be reduced particularly effectively.
[0354] The amounts of carbon fiber and thermoplastic resin fiber in the mixture can be appropriately set so that the weight ratio of these fibers in the resulting aggregate is the desired value. In particular, the contents of carbon fiber and thermoplastic resin fiber in the mixture can be 2.5% to 80% by weight, 5% to 70% by weight, or 10% to 60% by weight, respectively.
[0355] (Contains adhesive liquid)
[0356] Regarding the adhesive-containing liquid and its components, please refer to the above description of invention 1a.
[0357] It should be noted that, relative to the binder-containing liquid, the amount of binder can be 0.5% by weight or more, 1% by weight or more, 1.5% by weight or more, 2.0% by weight or more, or 3.0% by weight, and / or can be less than 20% by weight, less than 15% by weight, less than 10% by weight, less than 9% by weight, or less than 8% by weight. Particularly preferably, relative to the binder-containing liquid, the amount of binder is 1% to 10% by weight, or 2% to 8% by weight. Relative to the binder-containing liquid, the amount of solvent or dispersion medium can be 80% by weight or more, 85% by weight or more, 90% by weight or more, 92% by weight or more, or 93% by weight or more, and / or can be less than 99.9% by weight, less than 99.5% by weight, less than 99% by weight, or less than 98.5% by weight.
[0358] In addition, relative to the total amount of carbon fiber and thermoplastic resin fiber, the amount of adhesive is preferably 0.1% to 10% by weight, particularly preferably 0.5% to 9.0% by weight, 1.0% to 8.0% by weight, or 2.0% to 7.0% by weight.
[0359] (Fiber Opening)
[0360] The fiber components, especially carbon fibers, can be pre-treated by fiber opening. For details on fiber opening treatment, please refer to the above description related to invention 1a.
[0361] (mix)
[0362] There are no particular limitations on the method for obtaining the mixture from carbon fiber, thermoplastic resin fiber, and binder-containing liquid. The carbon fiber, thermoplastic resin fiber, and binder-containing liquid can be added to a container used in the granulation process in a mixed form. For example, the binder-containing liquid can be injected into blocks of carbon fiber and thermoplastic resin fiber, and the mixture can be obtained by random stirring before being added to a container. Alternatively, the carbon fiber, thermoplastic resin fiber, and binder-containing liquid can be added separately to a container and mixed within that container to form a mixture. Mixing and granulation can be carried out simultaneously.
[0363] The carbon fibers, thermoplastic resin fibers, and binder-containing liquids in the mixture may not need to be uniformly distributed within the mixture. The mixture can be stirred during the granulation process to improve uniformity.
[0364] <Granulation Process>
[0365] In the method disclosed in Invention 1b, a spindle-shaped precursor is produced by rotating the mixture in a container (hereinafter, sometimes referred to as "granulation process").
[0366] There are no particular limitations on the method of rotating the mixture in the container; known methods (especially known granulation methods) may be used.
[0367] In particular, a spindle-shaped precursor is produced by rotating the mixture within a container, in the gap between the container's inner wall and a rotating body within the container. This is not intended to be theoretically limited, but it is thought that by rotating a mixture containing carbon fiber and thermoplastic resin fiber, along with a binder liquid, within the gap between the container's inner wall and a rotating body within the container, the fibers are oriented in a specific direction and bonded together by the binder, resulting in a precursor with a spindle shape that can be obtained particularly effectively.
[0368] There are no particular limitations on the method used to rotate the mixture within the gap between the inner wall of the container and the rotating body inside the container. Regarding this method, reference may be made to the above description relating to invention 1a, except that the mixture contains carbon fibers, thermoplastic resin fibers, and a binder-containing liquid.
[0369] (Spindle-shaped precursor)
[0370] The spindle-shaped precursor contains carbon fibers and thermoplastic resin fibers, as well as a binder, and includes a liquid (especially water) from the binder-containing liquid. The liquid (especially water) in the precursor can be removed by the following drying process.
[0371] <Drying Process>
[0372] In the method disclosed herein, the obtained spindle-shaped precursor is dried.
[0373] There are no particular limitations on the method for drying the precursor; temperature and time conditions can be appropriately determined based on the moisture content of the obtained precursor. It should be noted that, in order to reduce the drying load, the spindle-shaped precursor can be dehydrated after the granulation process and before the drying process.
[0374] (Regarding Invention 2)
[0375] The carbon fiber reinforced thermoplastic resin particles disclosed in this invention 2 are characterized in that they comprise recycled carbon fibers and thermoplastic resin.
[0376] This recycled carbon fiber possesses a single-fiber tensile strength exceeding 3.0 GPa and a Weibull shape factor exceeding 6.0; and
[0377] It contains residual carbon components, which, relative to recycled carbon fibers, are more than 0% by weight and less than 5.0% by weight.
[0378] Typically, carbon fiber reinforced thermoplastic resin granules are obtained by melt-blending thermoplastic resin and carbon fiber using a twin-screw extruder or similar method. However, to achieve high-shear blending, the carbon fiber is sometimes pulverized within the extruder. If the average fiber length of the carbon fiber in the resulting granules is less than 300 μm, the mechanical property reinforcement effect will decrease.
[0379] Not to be limited by theory, the recycled carbon fiber involved in this invention 2 has a high Weibull shape factor at single fiber tensile strength, so the deviation of tensile strength is small. Even compared with ordinary unused carbon fiber with the same tensile strength, there are fewer single fibers with low tensile strength. Therefore, it is believed that single fiber breakage of recycled carbon fiber is relatively suppressed.
[0380] Furthermore, when the tensile strength of carbon fibers fed into the extruder typically varies greatly, low-strength fibers are pulverized more finely, resulting in a relatively high proportion of carbon fibers smaller than 300 μm remaining in the particles. On the other hand, as described above, since the recycled carbon fibers of Invention 2 of this disclosure have a high Weibull shape factor and a small variation in tensile strength, the proportion of fibers pulverized to smaller than 300 μm is reduced, resulting in a significant mechanical property enhancement effect.
[0381] In particular, a carbon fiber assembly can be used as the supply source of recycled carbon fiber when manufacturing the granules according to Invention 2 of this disclosure. The carbon fiber assembly comprises recycled carbon fiber and a binder. For a method of manufacturing it, see, for example, Japanese Patent No. 3452363 and Japanese Unexamined Patent Application Publication No. 2020-180421. A particularly preferred embodiment of the method according to this disclosure is a spindle-shaped carbon fiber assembly. For a method for obtaining a spindle-shaped carbon fiber assembly, see the above description according to Invention 1a.
[0382] By using spindle-shaped carbon fiber assemblies as the source of recycled carbon fiber, even recycled carbon fibers with low residual carbon content can achieve a particularly stable supply of thermoplastic resin.
[0383] Furthermore, not limited by theory, spindle-shaped carbon fiber assemblies are relatively easy to de-fiber through compounding in an extruder, and can be appropriately dispersed in thermoplastic resins without excessive compounding, thus enabling the production of short-fiber reinforced thermoplastic resin granules. Therefore, it is believed that the proportion of carbon fibers with longer fiber lengths in short-fiber reinforced thermoplastic resin granules can be further increased, thereby producing granules exhibiting particularly superior mechanical properties.
[0384] The invention disclosed herein will now be described in further detail. <Recycled carbon fiber (recycled carbon fiber material)>
[0385] Recycled carbon fiber (recirculated carbon fiber) contains carbon fiber components and carbon components other than the carbon fiber components (especially residual carbon components). Typically, in recycled carbon fiber, the carbon components other than the carbon fiber components are attached to the surface of the carbon fiber components.
[0386] The recycled carbon fiber disclosed herein is characterized by having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape factor of 6.0 or more; and containing residual carbon components, wherein the content of the residual carbon components is more than 0% by weight and less than 5.0% by weight relative to the recycled carbon fiber.
[0387] Any recycled carbon fiber with this characteristic is acceptable, and there are no particular restrictions on the recycling method. For example, it can be recycled carbon fiber obtained by heat-treating carbon fiber-reinforced plastic products such as carbon fiber reinforced plastic (CFRP).
[0388] Particularly preferred is that the recycled carbon fiber is obtained by the semiconductor thermal activation method (TASC method). That is, a particularly preferred embodiment of this disclosure includes recycled carbon fiber manufactured by decomposing the plastic components contained in a carbon fiber-containing plastic product using the semiconductor thermal activation method.
[0389] A method for obtaining recycled carbon fibers with the properties disclosed herein using a semiconductor thermal activation method is described below.
[0390] <Residual Average Fiber Length>
[0391] Preferably, the residual average fiber length of the recycled carbon fibers in the carbon fiber reinforced thermoplastic resin particles (i.e., the average fiber length of the recycled carbon fibers present in the particles) is 300 μm or more. More preferably, the residual average fiber length of the recycled carbon fibers is 320 μm or more, 330 μm or more, or 340 μm or more. There is no particular upper limit on the residual average fiber length of the recycled carbon fibers, and it can be 600 μm or less or 500 μm or less.
[0392] The residual average fiber length of recycled carbon fibers in carbon fiber reinforced thermoplastic granules can be obtained by removing the matrix resin from the granules using known decomposition methods (e.g., sulfuric acid decomposition, thermal decomposition, or solvent decomposition), filtering, and then measuring the fiber length of more than 300 individual fibers using a microscope, and calculating it as a numerical average.
[0393] <Frequency of occurrence of single fibers below 300μm>
[0394] Regarding the recycled carbon fibers in carbon fiber reinforced thermoplastic resin particles, the frequency of occurrence of single fibers with a diameter of 300 μm or less is preferably 40% or less. Particularly preferred frequencies are 39%, 38%, 37%, or 36% or less. There is no particular limitation on the lower limit of the frequency of occurrence of single fibers with a diameter of 300 μm or less; for example, it can be 1% or more or 10% or more.
[0395] The frequency of occurrence of single fibers below 300 μm can be obtained by measuring the fiber length of single fibers and calculating the proportion of fibers below 300 μm in the same manner as the determination of the residual average fiber length mentioned above.
[0396] <Single Fiber Tensile Strength>
[0397] The preferred tensile strength of a single fiber is 3.1 GPa or higher, 3.2 GPa or higher, 3.3 GPa or higher, or 3.4 GPa or higher. It should be noted that there is no specific upper limit on the tensile strength of a single fiber, and it can be below 6.0 GPa.
[0398] The tensile strength of a single fiber can be measured according to JIS R7606, as follows:
[0399] At least 30 individual fibers were collected from the fiber bundle.
[0400] The diameter of a single fiber is measured from a side image of the fiber taken using a digital microscope, and the cross-sectional area is calculated.
[0401] The sampled monofibers were fixed onto the perforated backing paper using an adhesive.
[0402] A paper insert with a fixed single fiber is mounted on a tensile testing machine. A tensile test is performed with a specimen length of 10 mm and a strain rate of 1 mm / min. The tensile breaking stress is then determined.
[0403] The tensile strength is calculated from the cross-sectional area of a single fiber and the tensile fracture stress.
[0404] The average tensile strength of at least 30 individual fibers is taken as the tensile strength of a single fiber.
[0405] <Weibull shape coefficient>
[0406] The preferred Weibull shape factor is 6.5 or higher, 7.0 or higher, 7.5 or higher, 8.0 or higher, or 8.5 or higher. There is no specific upper limit on the Weibull shape factor; it can be below 15.0. It should be noted that a high Weibull shape factor for single-fiber tensile strength implies a smaller deviation in single-fiber tensile strength.
[0407] The Weibull shape factor can be calculated using the following formula:
[0408] lnln{1 / (1-F)}=m×lnσ+C
[0409] In the formula, F is the failure probability obtained by the cumulative distribution method of symmetrical samples, σ is the tensile strength of a single fiber (MPa), m is the Weibull shape coefficient, and C is a constant.
[0410] By performing a Weibull plot using lnln{1 / (1-F)} and lnσ, the Weibull shape coefficient m can be obtained from the first-order approximate slope.
[0411] <Carbon fiber composition>
[0412] The carbon fiber component in recycled carbon fiber typically originates from carbon fiber contained in carbon fiber-containing products that serve as raw materials for recycled carbon fiber. The carbon fiber component in recycled carbon fiber can be modified through processes such as heat treatment during the manufacturing of recycled carbon fiber.
[0413] The carbon fiber components in recycled carbon fiber can be, for example, PAN-based carbon fiber or pitch-based carbon fiber.
[0414] There are no particular limitations on the morphology of the carbon fiber components in recycled carbon fiber; it can be a carbon fiber bundle composed of multiple single fibers (monofilaments, filaments). The number of filaments constituting the carbon fiber bundle can range from 1,000 to 80,000, or from 3,000 to 50,000. Furthermore, the diameter of the filaments constituting the carbon fiber components in recycled carbon fiber can be from 0.1 μm to 30 μm, 1 μm to 10 μm, or 3 μm to 8 μm.
[0415] <Residual carbon components>
[0416] The residual carbon component in recycled carbon fiber is particularly derived from the residual carbon in the resin contained in the carbon fiber-containing plastic products used as raw materials in the manufacture of recycled carbon fiber.
[0417] Preferably, the residual carbon content is 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less relative to the recycled carbon fiber. The residual carbon content is preferably minimized as much as possible, and may be 0.1% by weight or more, 0.2% by weight or more, 0.4% by weight or more, 0.6% by weight or more, 0.8% by weight or more, 1.0% by weight or more, or 1.2% by weight or more relative to the carbon fiber.
[0418] The residual carbon content in recycled carbon fibers can be measured by thermogravimetric analysis (TGA).
[0419] For the method for determining residual carbon content based on thermogravimetric analysis, please refer to the above description of Invention 1a.
[0420] <Thermoplastic Resins>
[0421] The thermoplastic resin contained in the carbon fiber reinforced thermoplastic resin particles disclosed herein may include, for example, polyolefin resins (e.g., polypropylene resin and polyethylene resin), polyester resins (e.g., polyethylene terephthalate resin, polybutylene terephthalate resin and polylactic acid resin), polyamide resins, polyetherketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins. The thermoplastic resin may be only one type, or it may be a mixture of two or more thermoplastic resins.
[0422] Granules
[0423] The carbon fiber reinforced thermoplastic resin particles disclosed herein comprise recycled carbon fibers and thermoplastic resin.
[0424] The shape of the carbon fiber reinforced thermoplastic resin particles involved in Invention 2 of this disclosure is not particularly limited, but the length of the particles in the long side direction is preferably 3 mm or more and 10 mm or less. Particularly preferred is that it can be 5 mm or less.
[0425] (Content of recycled carbon fiber)
[0426] Regarding the content of recycled carbon fiber in the carbon fiber reinforced thermoplastic particles involved in this invention 2, it is preferably 30% or less by weight, less than 30% by weight, 20% or less by weight, 15% or less by weight, and / or 5% or more by weight, 7% or more by weight, 8% or more by weight, or 10% or more by weight, relative to the carbon fiber reinforced thermoplastic resin particles.
[0427] If the content of recycled carbon fiber relative to the carbon fiber reinforced thermoplastic resin particles is 30% by weight or less, the carbon fiber can be dispersed particularly uniformly in the particles. Furthermore, if the content of recycled carbon fiber relative to the carbon fiber reinforced thermoplastic resin particles is 5% by weight or more, particularly good mechanical property reinforcement of the particles can be obtained.
[0428] <Methods for manufacturing granules>
[0429] The method for manufacturing the carbon fiber reinforced thermoplastic resin particles disclosed herein is not particularly limited; for example, it can be obtained by a manufacturing method including the following steps:
[0430] Provide recycled carbon fiber;
[0431] Thermoplastic resins are provided; and
[0432] Blending recycled carbon fiber and molten thermoplastic resin,
[0433] here,
[0434] Recycled carbon fibers possess a single-fiber tensile strength exceeding 3.0 GPa and a Weibull shape factor exceeding 6.0.
[0435] Recycled carbon fiber contains residual carbon components, which are more than 0% by weight and less than 5.0% by weight relative to recycled carbon fiber.
[0436] It should be noted that, regarding the recycled carbon fibers and thermoplastic resins used in manufacturing the carbon fiber reinforced thermoplastic resin particles involved in Invention 2 of this disclosure, refer to the above description relating to the carbon fiber reinforced thermoplastic resin particles involved in Invention 2 of this disclosure.
[0437] In the process of providing recycled carbon fiber, a spindle-shaped carbon fiber assembly can be used as the supply source of recycled carbon fiber. That is, when providing recycled carbon fiber, a spindle-shaped carbon fiber assembly containing recycled carbon fiber can be provided as recycled carbon fiber. Regarding the spindle-shaped carbon fiber assembly, refer to the above description relating to the spindle-shaped carbon fiber assembly of invention 1a of this disclosure. By using a spindle-shaped carbon fiber assembly as the supply source of recycled carbon fiber, the supplyability during pellet manufacturing can sometimes be further improved compared to using short fibers as the supply source of recycled carbon fiber. There is no particular limitation on the method for manufacturing the spindle-shaped carbon fiber assembly; preferably, the spindle-shaped carbon fiber assembly can be manufactured according to the manufacturing method of the carbon fiber assembly of invention 1a of this disclosure.
[0438] In one exemplary embodiment for manufacturing the carbon fiber reinforced thermoplastic resin granules involved in this disclosure, thermoplastic resin as a base material is supplied via the main feeder of a twin-screw compounding extruder, and recycled carbon fibers (particularly spindle-shaped recycled carbon fiber assemblies) are supplied to the resin being compounded and melted in the extruder via the twin-screw feeder. The extruded compound is cooled via a water-cooling path and then cut to obtain carbon fiber reinforced thermoplastic resin granules.
[0439] Molded Products
[0440] Molded articles can be manufactured by molding the carbon fiber reinforced thermoplastic resin granules disclosed herein using an extrusion molding machine or the like. Molded articles made using the granules disclosed herein exhibit good physical properties, particularly good mechanical properties.
[0441] Tensile Strength
[0442] According to ISO 527, molded articles manufactured according to the method shown in the examples preferably exhibit a tensile strength of 90 MPa or more, particularly preferably 92 MPa to 110 MPa, or 95 MPa to 100 MPa.
[0443] <Bending Strength>
[0444] According to ISO 178, molded articles manufactured according to the method shown in the examples preferably exhibit a flexural strength of 140 MPa or more, particularly preferably 140 MPa to 160 MPa, 140 MPa to 150 MPa, or 140 MPa to 145 MPa.
[0445] <Flexural modulus>
[0446] According to ISO 178, the molded articles manufactured according to the method shown in the examples preferably exhibit a flexural modulus of 7100 MPa or more, particularly preferably 7100 MPa to 8000 MPa, 7100 MPa to 7500 MPa, or 7100 MPa to 7400 MPa.
[0447] Manufacturing Method of Regenerated Carbon Fiber Based on Semiconductor Thermal Activation
[0448] The following describes a method for obtaining recycled carbon fibers with the properties disclosed in Invention 2 using a semiconductor thermal activation method. First, a method for decomposing plastic-containing materials will be described, followed by a method for recovering inorganic materials (carbon fibers) from plastic-containing materials containing both plastic and inorganic materials (carbon fibers) using this decomposition method.
[0449] <Methods for decomposing plastic-containing materials>
[0450] The methods for decomposing plastic-containing materials disclosed herein include:
[0451] In an environment within a heating furnace where a low-oxygen-concentration gas with an oxygen concentration of less than 10% by volume is introduced, a plastic-containing material is heated to a first surface temperature in the presence of a semiconductor material, thereby decomposing the plastic in the plastic-containing material.
[0452] Figure 2 This is a conceptual cross-sectional diagram used to illustrate the decomposition method involved in this invention. The decomposition mechanism of plastic-containing materials involved in this invention will be described below. It should be noted that this invention is not intended to be theoretically limited.
[0453] It is believed that if semiconductor material 11 is heated in an oxygen environment, positive holes h will be generated in semiconductor material 11. + and electronic e - The electron e - It reacts with oxygen (O2) in the environment to produce O2. - Free radicals (reactive oxygen species). Then, in the plastic-containing material 12 disposed adjacent to the semiconductor material 11, free radical propagation occurs, and the plastic-containing material 12 decomposes into small molecule components, which are then oxidized and decomposed into decomposition gases such as CO2, H2O, and CH4. It is believed that free radicals promote the oxidative decomposition of plastic by extracting hydrogen from the plastic.
[0454] By using semiconductor materials, the heat introduced for the decomposition of plastics can be reduced compared to not using semiconductor materials, resulting in a reduction in energy consumption.
[0455] Existing semiconductor-based thermal activation methods for plastic decomposition sometimes generate excessive oxidative heat during the heat treatment process. In these methods, because the heat treatment is carried out in an atmosphere with uncontrolled oxygen concentration, excess free radicals are generated, resulting in excessive oxidative heat.
[0456] In contrast, the inventors of this application have discovered that even in the presence of semiconductor materials, by setting the oxygen concentration to a low value, it is possible to effectively heat-treat plastics while suppressing excessive oxidative heat generation.
[0457] In particular, during the initial stages of the thermal decomposition of plastics, the large quantity of plastic can easily lead to excessive oxidative heat generation. In contrast, the method disclosed herein effectively suppresses excessive oxidative heat generation even in the initial stages of decomposition because the heating treatment is performed at a lower oxygen concentration.
[0458] Therefore, according to the method disclosed herein, since the heating process is performed in the presence of semiconductor materials, good decomposition efficiency can be obtained even at low oxygen concentrations. Furthermore, by setting the oxygen concentration in the heating furnace to a low value, excessive oxidative heating can be suppressed, thereby achieving decomposition processing with improved stability.
[0459] The decomposition method involved in the present invention will be described with reference to the accompanying drawings depicting exemplary embodiments.
[0460] Figure 3 This is a cross-sectional view schematically showing one embodiment of the decomposition method involved in this disclosure. Figure 3 The heating furnace 20 shown has a heat source (heater) 23, a gas supply section 24, an exhaust port 25, and an internal space 26. A porous carrier 21 is disposed within the internal space 26 of the heating furnace 20, and semiconductor material is supported on the surface of the carrier 21. Figure 3 In one embodiment, the plastic material 22 is disposed in contact with the carrier 21.
[0461] The ambient temperature of the internal space 26 of the heating furnace 20 is controlled by the heat source (heater) 23, thereby allowing the surface temperature of the plastic material 22 to reach a specific temperature. The surface temperature of the plastic material 22 can be measured by a temperature sensor 27 disposed within 5 mm of the surface of the plastic material 22.
[0462] Low-oxygen-concentration gas (with an oxygen concentration of less than 10% by volume) is introduced into the internal space 26 of the furnace 20 via the gas supply section 24. The oxygen concentration within the furnace 20 can be controlled by setting the introduction rate of the low-oxygen-concentration gas according to the furnace's internal volume. The low-oxygen-concentration gas can be introduced into the furnace, for example, by being forced into the furnace via the gas supply section located within the furnace, or by being drawn into the furnace by applying suction pressure to the exhaust port 25.
[0463] Low-oxygen-concentration gases are, for example, a mixture of air and nitrogen. The oxygen concentration inside the furnace can be controlled by selecting the ratio of air to nitrogen.
[0464] In an environment where the oxygen concentration is controlled to less than 10% by introducing a low-oxygen gas, the plastic-containing material is heated to a first surface temperature, for example, 300°C to 600°C. As a result, the plastic contained in the plastic-containing material 22 is decomposed into decomposition gases such as water vapor, carbon dioxide, and methane, which are discharged from the exhaust port 25 of the heating furnace 20.
[0465] After the above-mentioned heat treatment with an oxygen concentration of less than 10% by volume, a further heat treatment with an oxygen concentration of more than 10% by volume can be carried out.
[0466] In addition, inorganic materials contained in plastic materials can be recycled after heat treatment.
[0467] The decomposition method involved in this disclosure will now be described in more detail.
[0468] <Including plastic materials>
[0469] Plastic-containing materials contain plastic. Plastic-containing materials can be either plastic materials or plastic composites.
[0470] Plastics contained in plastic materials can be categorized as thermoplastic resins and thermosetting resins.
[0471] Examples of thermoplastic resins contained in plastic materials include: polycarbonate (PC) resin, polyethylene (PE) resin, polypropylene (PP) resin, polyvinyl chloride (PVC) resin, polystyrene (PS) resin, polyethylene terephthalate (PET) resin, acrylonitrile-butadiene-styrene (ABS) resin, polyamide (PA) resin, polylactic acid (PLA) resin, polyimide (PI) resin, polymethyl methacrylate (PMMA) resin, methacrylic acid resin, polyvinyl alcohol (PVA) resin, polyacetal resin, petroleum resin, aspartate resin, modified polyphenylene ether resin, polybutylene terephthalate (PBT) resin, polybutene (PB) resin, fluoropolymer resin, polyacrylate resin, polyether ether ketone (PEEK) resin, and polyphenylene sulfide (PPS) resin.
[0472] Examples of thermosetting resins contained in plastic materials include: phenolic resin, urethane foam resin, polyurethane resin, urea resin, epoxy resin, unsaturated polyester resin, melamine resin, alkyd resin, vinyl ester resin, and cyanate ester resin.
[0473] The plastic material may contain at least one of the above-mentioned thermoplastic resins and thermosetting resins.
[0474] (Plastic composite materials)
[0475] This includes plastic materials, especially plastic composites. Examples of plastic composites include fiber-reinforced plastics (FRP). Examples of reinforcing fibers contained in fiber-reinforced plastics include carbon fiber.
[0476] (Carbon fiber reinforced plastic)
[0477] Plastic composites, particularly carbon fiber reinforced plastics (CFRP) and other carbon fiber-containing plastic products. CFRP contains both plastic and carbon fiber material (carbon fiber). CFRP may also include other components and / or materials (e.g., reinforcing fibers other than carbon fiber, resin moldings, metals, ceramics, etc.).
[0478] There are no particular limitations on the carbon fibers contained in carbon fiber reinforced plastics; examples include PAN-based carbon fibers and pitch-based carbon fibers. The carbon fiber can be one type or composed of two or more types.
[0479] The carbon fiber material contained in carbon fiber reinforced plastics can be in any form, such as carbon fiber bundles, fabrics formed from carbon fiber bundles, or carbon fiber nonwoven fabrics.
[0480] <Introduction of low-oxygen gas>
[0481] In the methods disclosed herein,
[0482] Introduce a low-oxygen-concentration gas (less than 10% by volume) into the environment of the heating furnace.
[0483] Preferably, the oxygen concentration of the low-oxygen gas introduced into the heating furnace environment is greater than 0% by volume and is 1% or more, 2% or more, 3% or more or 4% or more, and / or less than 9% by volume, less than 8% by volume, or less than 7% by volume.
[0484] The timing for introducing a low-oxygen-concentration gas into the heating furnace can be determined based on the type of plastic contained in the plastic material and the surface temperature at which the plastic begins to decompose. Alternatively, the timing can also be determined based on prior data regarding the self-heating of the plastic material.
[0485] In one preferred embodiment of this disclosure, a low-oxygen-concentration gas is introduced into the aforementioned environment of the heating furnace while the surface temperature of the plastic-containing material is maintained below 300°C within the heating furnace.
[0486] More preferably, a low-oxygen-concentration gas with an oxygen concentration of less than 10% by volume is introduced into the environment of the heating furnace while the surface temperature of the plastic material is maintained below 250°C, below 200°C, or below 150°C.
[0487] More preferably, a low-oxygen concentration gas with an oxygen concentration of less than 10% by volume is introduced into the environment of a heating furnace containing a plastic material with a surface temperature maintained below 300°C, thereby reducing the oxygen concentration in the furnace environment to less than 10% by volume. It should be noted that when introducing a low-oxygen concentration gas with an oxygen concentration of less than 10% by volume into the furnace environment, there is no particular limitation on the lower limit of the surface temperature of the plastic material maintained in the furnace; for example, it can be above 0°C, above 10°C, above 20°C, or above room temperature.
[0488] More preferably, a low-oxygen-concentration gas with an oxygen concentration of less than 10% by volume is introduced into the environment of the heating furnace, particularly into the environment of a heating furnace containing plastic materials where the surface temperature is maintained below 300°C, thereby controlling the oxygen concentration in the environment of the heating furnace to be greater than 0% by volume and more than 1%, more than 2%, more than 3%, or more than 4%, and / or less than 9%, less than 8%, or less than 7%.
[0489] The oxygen concentration inside the heating furnace can be directly measured using an oxygen concentration meter (oxygen monitor), or it can be determined based on the furnace's internal volume and the amount of gas introduced into the furnace. The preferred oxygen concentration inside the heating furnace is the average oxygen concentration during the heating process.
[0490] The introduction of low-oxygen-concentration gas into the furnace can be achieved, for example, by forcing the low-oxygen-concentration gas into the furnace through a gas supply section located in the furnace, or by drawing gas in from an intake port (or exhaust port) located in the furnace, thereby allowing the gas to flow into the furnace from a gas supply section located at a different position than the intake port. The gas supply section of the furnace may, for example, have an opening and / or may have a permeable material.
[0491] The amount of gas introduced into the furnace can be set based on the unit amount of resin to be decomposed (e.g., epoxy resin), according to the capacity of the heating furnace and the desired oxygen concentration.
[0492] For example, the gas introduction rate in the furnace per unit amount of resin is in the range of 1 to 1000 (L / min) / kg or less, and preferably in the range of 2 to 700 (L / min) / kg or less. Furthermore, the time required to replace the furnace environment with the introduced gas can be determined based on the determined gas introduction rate and the volume of the heating furnace used.
[0493] In particular, by setting the amount of low-oxygen-concentration gas introduced relative to the furnace volume, the environment inside the furnace can be replaced by the introduced low-oxygen-concentration gas while the surface temperature of the plastic material is kept below 300°C inside the furnace.
[0494] The low-oxygen-concentration gas introduced into the heating furnace may include diluent gases, particularly a mixture of air and diluent gases. Examples of diluent gases include nitrogen, carbon dioxide, water vapor, and superheated steam. It should be noted that superheated steam is water vapor heated to a temperature above its boiling point. Superheated steam has the advantage of high heat transfer to the material being decomposed.
[0495] (Heating furnace)
[0496] The heating furnace can be a combustion furnace or an electric furnace. For example, the heating furnace may include: an internal space for accommodating materials containing plastics and semiconductors; a heat source (heater) for heating the environment inside the furnace; a gas supply unit for introducing low-oxygen-concentration gas into the furnace; an exhaust port for discharging decomposition gases; and a suction port for arbitrarily applying suction pressure to the interior of the furnace. It should be noted that a single structure can also be used for both the exhaust port and the suction port. For example, one or more openings located within the heating furnace can be used as the exhaust port and / or suction port.
[0497] (Surface temperature)
[0498] The "surface temperature" of plastic-containing materials can be determined by measuring the temperature within 5 mm around the plastic-containing material during heat treatment.
[0499] The surface temperature of plastic materials can be controlled, for example, by controlling the temperature inside the furnace via the heat source of the furnace, and / or by introducing low-temperature gas into the furnace and / or reducing the oxygen concentration to suppress oxidative heating.
[0500] Alternatively, the surface temperature of the plastic material can be measured by a temperature sensor positioned within 5 mm of the surface of the plastic material, and the measured value can be fed back to the heat source of the heating furnace, thereby enabling further high-precision control of the surface temperature.
[0501] Moreover, data on the temperature inside the heating furnace and / or the output power of the heat source relative to the surface temperature measured by a sensor can be obtained in advance, and heating treatment can be performed based on this data.
[0502] <Heat Treatment>
[0503] The methods involved in this disclosure include:
[0504] In an environment within a heating furnace where a low-oxygen-concentration gas with an oxygen concentration of less than 10% by volume is introduced, a plastic-containing material is heated to a first surface temperature in the presence of a semiconductor material, thereby decomposing the plastic in the plastic-containing material.
[0505] Preferably, the heat treatment is carried out in an environment where the oxygen concentration is less than 10% by introducing a low-oxygen gas with an oxygen concentration of less than 10% by volume, in particular at an oxygen concentration of more than 0%, 1% or more, 2% or more, 3% or more, or 4% or more, and / or at an oxygen concentration of less than 9%, 8% or less, or 7% or less.
[0506] (First surface temperature)
[0507] "First surface temperature" refers to the surface temperature of the plastic-containing material. Similar to the "surface temperature" mentioned above, the "first surface temperature" can be determined by measuring the temperature within 5 mm of the plastic-containing material during heat treatment.
[0508] The first surface temperature can be above 300°C, above 325°C, or above 350°C, and / or can be below 600°C, below 550°C, below 500°C, or below 450°C. For example, the first surface temperature is 300°C to 600°C, 300°C to 550°C, 300°C to 500°C, or 300°C to 450°C.
[0509] If the temperature of the first surface is below the aforementioned range, plastic decomposition may not occur. However, if the temperature of the first surface exceeds the aforementioned range, in cases where the plastic material contains valuable materials such as carbon fibers, the degradation and / or burning of these valuable materials during heating in the presence of oxygen may become significant. By setting the temperature of the first surface to a lower level, the effect of suppressing excessive oxidative heating is further improved.
[0510] In a preferred embodiment of this disclosure, during heat treatment with an oxygen concentration of less than 10% by volume, the temperature of the first surface is raised to a temperature of 450°C or higher. At lower heating temperatures, further decomposition of the plastic can sometimes be inhibited due to the formation of carbides on the surface of the plastic material. By raising the surface temperature to 450°C or higher, carbides can be removed even at lower oxygen concentrations. Therefore, the decomposition efficiency of the plastic can be further improved.
[0511] Preferably, the heating treatment is performed for a specified time under a low-oxygen concentration gas with an oxygen concentration of less than 10% by volume. This specified time can be from 1 minute to 600 minutes, preferably from 30 minutes to 300 minutes, and more preferably from 60 minutes to 180 minutes. It should be noted that the starting point of the aforementioned "specified time" can be the point at which the furnace temperature reaches 300°C or the point at which the plastic begins to decompose.
[0512] (Semiconductor materials)
[0513] Semiconductor materials can be placed together with plastic materials in a heating furnace, or the semiconductor materials can be placed in the heating furnace beforehand, and then the plastic materials can be placed adjacent to or in contact with the semiconductor materials.
[0514] In one embodiment of this disclosure, a heat-treated plastic material and a semiconductor material are disposed apart from each other at a distance of 50 mm or less. For this purpose, a spacer disposed between the plastic material and the semiconductor material may be used, for example. It should be noted that in this case, there is no particular limitation on the lower limit of this distance, which may exceed 0 mm, exceed 1 mm, exceed 5 mm, or exceed 10 mm.
[0515] The distance between plastic and semiconductor materials can be measured when they are closest to each other.
[0516] In other preferred embodiments covered by this disclosure, the plastic material to be heat-treated is configured to come into contact with the semiconductor material.
[0517] There are no particular limitations on the contact method between the plastic material and the semiconductor material. For example, the two can be brought into contact by depositing the plastic material on the semiconductor material. Alternatively, the plastic material can be deposited on the semiconductor material supported on the surface of the carrier. Furthermore, the two can also be brought into contact by surrounding or covering at least a portion or all of the plastic material with the semiconductor material.
[0518] There are no particular limitations on the semiconductor material, as long as it is stable at the temperature and oxygen concentration of this invention. The semiconductor material may contain, for example, at least one selected from the following substances:
[0519] BeO, MgO, CaO, SrO, BaO, CeO2, ThO2, UO3, U3O8, TiO2, ZrO2, V2O5, Y2O3, Y2O2S, Nb2O5, Ta2O5, MoO3, WO3, MnO2, Fe2 O3, MgFe2O4, NiFe2O4, ZnFe2O4, ZnCo2O4, ZnO, CdO, Al2O3, MgAl2O4, ZnAl2O4, Tl2O3, In2O3, SiO2, SnO2, PbO2, UO 2. Cr2O3, MgCr2O4, FeCrO4, CoCrO4, ZnCr2O4, WO2, MnO, Mn3O4, Mn2O3, FeO, NiO, CoO, Co3O4, PdO, CuO, Cu2O, Ag2O, CoAl2O4, NiAl2O4, Tl2O, GeO, PbO, TiO, Ti2O3, VO, MoO2, IrO2, RuO2, CdS, CdSe, CdTe, Cu2O, Sb2O3, MnO3 and CoCrO4.
[0520] Preferably, the semiconductor material is an oxide semiconductor material. Examples of preferred oxide semiconductor materials include: chromium oxide, titanium oxide, zinc oxide, vanadium oxide, tungsten oxide, molybdenum oxide, cobalt oxide, iron oxide, and copper oxide.
[0521] There are no particular limitations on the morphology of the semiconductor material; it can be plate-like, granular, or honeycomb-like. From the viewpoint of promoting plastic decomposition, it is preferable to support the semiconductor material on the surface of a breathable carrier. The breathable carrier can be a porous body or a honeycomb support made of ceramics, etc. The semiconductor material can be a sintered semiconductor.
[0522] <Two-stage heating>
[0523] The heat treatment method involved in one preferred embodiment of this disclosure includes:
[0524] A plastic material subjected to heat treatment at a first surface temperature is heated in the presence of a semiconductor material in an environment with an oxygen concentration of 10% by volume or higher.
[0525] Heat treatment with an oxygen concentration of 10% by volume or more is preferably carried out at an oxygen concentration of more than 10%, 12% by volume or more, 15% by volume or more, or 20% by volume or more, and / or at an oxygen concentration of less than 30% by volume or less than 25% by volume.
[0526] In this scheme, which is also mentioned as a two-stage heating process, the plastic material that has been heated at a lower oxygen concentration is further heated at an increased oxygen concentration.
[0527] In the initial stage of the thermal decomposition of plastics, the large amount of plastic can easily lead to excessive oxidative heat generation. In contrast, in the above embodiment with two-stage heating, a heating treatment at a lower oxygen concentration is followed by a heating treatment that increases the oxygen concentration. That is, by increasing the oxygen concentration during the stage where the amount of plastic decreases due to decomposition, the generation of excessive oxidative heat can be suppressed.
[0528] Furthermore, in heat treatment at lower oxygen concentrations, sometimes a portion of the plastic fails to vaporize and remains as carbonaceous material. In contrast, in the above-described embodiment with two-stage heating, the residual carbonaceous material can be effectively decomposed / removed due to the increased oxygen concentration for further heat treatment, resulting in a further improvement in decomposition efficiency.
[0529] Heating treatment with a low oxygen concentration of less than 10% by volume and heating treatment with an oxygen concentration of 10% by volume or more can be performed continuously in the same furnace. That is, for example, after heating the plastic material to a first surface temperature, the oxygen concentration can be increased to 10% by volume or more in the same furnace for further heating treatment. In existing plastic decomposition methods, fine cutting and other processing of the material to be processed are required after batch processing. However, by continuously performing heating treatment with a low oxygen concentration of less than 10% by volume and heating treatment with an oxygen concentration of 10% by volume or more in the same furnace, the number of processes can be reduced.
[0530] An environment with an oxygen concentration of 10% by volume or more can be created, for example, by introducing a gas with a high oxygen concentration of 10% by volume or more into a heating furnace, particularly by introducing air and / or oxygen into the heating furnace. The oxygen concentration of the high oxygen concentration gas can be more than 10% by volume, more than 12% by volume, more than 15% by volume, or more than 20% by volume, and / or less than 30% by volume or less than 25% by volume.
[0531] In heat treatment with an oxygen concentration of 10% or more, semiconductor materials used in heat treatment at the first surface temperature can be used.
[0532] (Second surface temperature)
[0533] In particular, in the presence of semiconductor materials and in an environment with an oxygen concentration of 10% by volume or more, a plastic material subjected to heat treatment at a first surface temperature is heated to a second surface temperature.
[0534] "Second surface temperature" refers to the surface temperature of the plastic-containing material being processed. Similar to the "surface temperature" and "first surface temperature" mentioned above, the "second surface temperature" can be determined by measuring the temperature within 5 mm around the plastic-containing material during the heat treatment.
[0535] The temperature of the second surface can be in the range of 400°C to 600°C. More preferably, the temperature of the second surface is 425°C to 575°C or 450°C to 550°C.
[0536] If the temperature of the second surface is below the above range, the improvement in decomposition efficiency may not be observed. Furthermore, if the temperature of the second surface exceeds the above range, in cases where the plastic material contains valuable materials such as carbon fibers, the degradation and / or burning of these valuable materials due to heating in the presence of oxygen may become significant.
[0537] The second surface temperature can be substantially the same as the first surface temperature.
[0538] In addition, the temperature of the second surface can be higher than or at least 5°C, 10°C, 25°C, 50°C, or 75°C higher than the temperature of the first surface. There is no particular limit to the upper limit of the difference between the temperature of the first surface and the temperature of the second surface; for example, it can be below 200°C or below 100°C.
[0539] Heating treatment with an oxygen concentration of 10% by volume or higher can be performed within a specified time. This specified time can be, for example, 1 minute to 600 minutes, 60 minutes to 360 minutes, or 90 minutes to 300 minutes.
[0540] <Applications>
[0541] The decomposition method for plastic-containing materials disclosed herein can effectively vaporize and decompose a wide variety of plastics. Furthermore, the decomposition method disclosed herein is also applicable to volatile organic compounds (VOCs), exhaust gases, particulate matter (PM), etc., and can be used for exhaust gas treatment.
[0542] Methods for the Recycling of Inorganic Materials
[0543] The following describes the methods involved in this disclosure for recycling inorganic materials contained in plastic composite materials.
[0544] In one embodiment of the recycling method disclosed herein, the plastic-containing material, as a plastic composite material, contains both plastic and inorganic materials, and the recycling method includes:
[0545] The above decomposition method is used to decompose the plastic in plastic-containing materials and recover the inorganic materials.
[0546] It should be noted that the decomposition methods involved in this disclosure and their details can be found in the above description of decomposition methods for plastic-containing materials.
[0547] As described above, the decomposition method disclosed herein can effectively decompose plastics. Therefore, the recycling method disclosed herein can effectively and selectively decompose the plastics contained in plastic composite materials, thereby effectively recycling inorganic materials with good physical properties.
[0548] Furthermore, the recycling method disclosed herein allows for the recycling of inorganic materials without the need to crush the plastic composite material. It should be noted that crushing the plastic composite material does not require special exclusion and can be performed arbitrarily.
[0549] Furthermore, in the case of recovering inorganic materials from plastic composites, from the viewpoint of maintaining the quality of the recovered inorganic materials, it is necessary to minimize the impact of heat treatment on the inorganic materials. In this regard, in the decomposition method disclosed herein, excessive oxidative heating is suppressed by using a low oxygen concentration. Therefore, according to the recovery method disclosed herein, inorganic materials with relatively good physical properties can be recovered.
[0550] (Two-stage heating)
[0551] In other embodiments of the recycling method disclosed herein, the plastic-containing material, which is a plastic composite material, is subjected to two-stage heating. That is, the plastic is decomposed and the inorganic material is recovered by subjecting the plastic composite material to heating under a low-oxygen-concentration gas (oxygen concentration less than 10%) and subsequent heating treatment with an oxygen concentration of 10% by volume or more.
[0552] In the recycling of inorganic materials, it is desirable to suppress the deterioration of the inorganic materials' properties caused by excessive oxidative heating. Furthermore, it is preferable to suppress the deterioration of the inorganic materials' properties caused by the carbonization of plastics, which adheres to and remains on the inorganic materials. In this regard, in a scheme where the plastic composite material is subjected to two-stage heating, a lower oxygen concentration is achieved in the initial stage where excessive oxidative heating is likely to occur, thus suppressing the deterioration of the inorganic materials' properties caused by excessive oxidative heating. Moreover, subsequent heating treatment with a higher oxygen concentration effectively removes the carbonized resin remaining on the inorganic materials. As a result, the inorganic material recycling method via two-stage heating treatment ensures better physical properties of the recycled inorganic materials.
[0553] (Inorganic materials)
[0554] Examples of plastic composite materials containing inorganic materials and plastics include fiber-reinforced plastics (FRP), especially carbon fiber reinforced plastics.
[0555] Inorganic materials, especially carbon fiber (carbon fiber materials).
[0556] (Carbon fiber)
[0557] There are no particular limitations on the carbon fibers contained in carbon fiber reinforced plastics; examples include PAN-based carbon fibers and pitch-based carbon fibers. The carbon fiber can be one type or composed of two or more types.
[0558] The carbon fibers contained in carbon fiber reinforced plastics can be in any form, such as carbon fiber bundles, fabrics formed from carbon fiber bundles, or carbon fiber nonwoven fabrics.
[0559] (Recyclables)
[0560] According to one embodiment of the recycling method disclosed herein, the residual carbon from plastics recycled together with inorganic materials is reduced, particularly to less than 5% by weight of the recycled inorganic materials. Preferably, the residual carbon is less than 4%, 3%, 2%, 1%, 0.9%, 0.5%, or 0.1% by weight of the recycled inorganic materials. It should be noted that the residual carbon is preferably reduced as much as possible, with a lower limit of more than 0.001% by weight. The amount of residual carbon in the recycled inorganic materials can be measured in the same manner as the amount of residual carbon in the recycled carbon fibers described later.
[0561] Moreover, according to the recycling method disclosed herein, carbon fibers with superior physical properties compared to those produced before carbon fiber reinforced plastics can be recycled.
[0562] In particular, according to the recycling method disclosed herein, carbon fibers with a single fiber tensile strength of 3.0 GPa or more and a Weibull shape factor of 6.0 or more can be obtained from carbon fiber reinforced plastics as inorganic materials.
[0563] (Single fiber tensile strength)
[0564] The preferred tensile strength of a single fiber is 3.1 GPa or higher, 3.2 GPa or higher, 3.3 GPa or higher, or 3.4 GPa or higher. It should be noted that there is no specific upper limit on the tensile strength of a single fiber, and it can be below 6.0 GPa.
[0565] The tensile strength of a single fiber can be measured according to JIS R7606 as follows:
[0566] At least 30 individual fibers are collected from the fiber bundle.
[0567] In a side view image of a single fiber taken using a digital microscope, the diameter of the single fiber is measured, and the cross-sectional area is calculated.
[0568] The sampled monofibers were fixed onto the perforated backing paper using an adhesive.
[0569] A paper insert with a fixed single fiber is mounted on a tensile testing machine. A tensile test is performed with a specimen length of 10 mm and a strain rate of 1 mm / min. The tensile breaking stress is then determined.
[0570] The tensile strength is calculated from the cross-sectional area of a single fiber and the tensile fracture stress.
[0571] The average tensile strength of at least 30 individual fibers is taken as the tensile strength of a single fiber.
[0572] (Weibull shape coefficient)
[0573] The preferred Weibull shape factor is 6.5 or higher, 7.0 or higher, 7.5 or higher, 8.0 or higher, or 8.5 or higher. There is no specific upper limit on the Weibull shape factor; it can be below 15.0. It should be noted that a high Weibull shape factor for single-fiber tensile strength implies a smaller deviation in single-fiber tensile strength.
[0574] The Weibull shape factor can be calculated using the following formula:
[0575] lnln{1 / (1-F)}=m×lnσ+C
[0576] In the formula, F is the failure probability obtained by the cumulative distribution method of symmetrical samples, σ is the tensile strength of a single fiber (MPa), m is the Weibull shape coefficient, and C is a constant.
[0577] By performing a Weibull plot using lnln{1 / (1-F)} and lnσ, the Weibull shape coefficient m can be obtained from the first-order approximate slope.
[0578] <Applications>
[0579] According to the recycling methods disclosed herein, for example, only the matrix resins of fiber-reinforced plastics (FRP), solar panels, electronic circuits, etc., can be effectively decomposed, and valuable materials such as reinforcing fibers and rare metals can be effectively recovered.
[0580] Recycled Carbon Fiber
[0581] The recycled carbon fiber (recycled carbon fiber material) disclosed herein can be manufactured by recycling carbon fiber from carbon fiber reinforced plastics. In one embodiment of this disclosure, the recycled carbon fiber may have superior physical properties compared to the carbon fiber before manufacturing the carbon fiber reinforced plastic.
[0582] There are no particular limitations on the method for manufacturing recycled carbon fiber. For example, recycled carbon fiber can be manufactured by recycling carbon fiber from carbon fiber reinforced plastics according to the recycling method disclosed herein.
[0583] In one embodiment, the recycled carbon fiber has a single-fiber tensile strength of 3.0 GPa or higher and a Weibull shape factor of 6.0 or higher. The single-fiber tensile strength and Weibull shape factor can be measured and determined according to the methods described above.
[0584] The preferred tensile strength of a single fiber in recycled carbon fiber is 3.1 GPa or higher, 3.2 GPa or higher, 3.3 GPa or higher, or 3.4 GPa or higher. There is no particular upper limit on the tensile strength of a single fiber, and it can be below 6.0 GPa.
[0585] The Weibull shape factor of recycled carbon fiber is preferably 6.5 or higher, 7.0 or higher, 7.5 or higher, 8.0 or higher, or 8.5 or higher. There is no particular upper limit on the Weibull shape factor, and it can be below 15.0.
[0586] (Manufacturing method of recycled carbon fiber)
[0587] In particular, a method for manufacturing recycled carbon fibers, wherein the recycled carbon fibers have a single fiber tensile strength of 3.0 GPa or higher and a Weibull shape factor of 6.0 or higher, and the content of residual carbon components relative to the recycled carbon fibers is more than 0% by weight and less than 5.0% by weight, the method comprising:
[0588] In a furnace environment with a low oxygen concentration (less than 10% by volume) introduced into the heating furnace, in the presence of a semiconductor material, a plastic-containing material is heated to a first surface temperature, decomposing the plastic within the material.
[0589] Here, the plastic material is carbon fiber reinforced plastic containing carbon fiber.
[0590] Furthermore, a method for manufacturing recycled carbon fibers, wherein the recycled carbon fibers have a single fiber tensile strength of 3.0 GPa or higher and a Weibull shape factor of 6.0 or higher, and the content of residual carbon components relative to the recycled carbon fibers is more than 0% by weight and less than 5.0% by weight, the method comprising:
[0591] In a furnace environment with a low oxygen concentration of less than 10% by volume, and in the presence of a semiconductor material, a plastic-containing material is heated to a first surface temperature. Then, the plastic-containing material subjected to heat treatment at the first surface temperature is heated again in the presence of the semiconductor material in an environment with an oxygen concentration of 10% by volume or higher, thereby decomposing the plastic in the plastic-containing material.
[0592] Here, "containing plastic" refers to carbon fiber reinforced plastic.
[0593] In one preferred embodiment of the method for manufacturing recycled carbon fiber disclosed herein, a low-oxygen-concentration gas is introduced into the environment of the heating furnace while the surface temperature of the plastic is below 300°C.
[0594] (Residual carbon)
[0595] Preferably, in the recycled carbon fiber involved in this disclosure, the residual carbon content is reduced, particularly the residual carbon content is 5% by weight or less relative to the recycled carbon fiber. More preferably, the residual carbon content is 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.9% by weight or less, 0.5% by weight or less, or 0.1% by weight or less relative to the recycled carbon fiber.
[0596] It should be noted that "residual carbon" refers to the carbonized components of the plastic contained in the carbon fiber reinforced plastic used as a raw material in the manufacture of recycled carbon fiber.
[0597] The amount of residual carbon in recycled carbon fibers can be determined by thermogravimetric analysis (TGA).
[0598] For the determination of residual carbon content based on thermogravimetric analysis, please refer to the above description of Invention 1a.
[0599] Manufacturing Method of Spindle-Shaped Carbon Fiber Assemblies
[0600] Regarding Invention 2, and the spindle-shaped carbon fiber assembly and its manufacturing method, please refer to the above description relating to Invention 1a. Furthermore, for details regarding the recycled carbon fibers contained in the carbon fiber assembly, please refer to the above description relating to Invention 1a, and also to the above description relating to the recycled carbon fibers of Invention 2.
[0601] Example
[0602] The present invention will be further described in detail below with reference to embodiments. It should be noted that the embodiments are examples and this application is not limited thereto.
[0603] Embodiment A1 of Invention 1a
[0604] <Material Modulation>
[0605] (Recycled carbon fiber)
[0606] As recycled carbon fiber, recycled carbon fiber with a residual carbon content of 1.4% by weight obtained by semiconductor thermal activation method is used.
[0607] The amount of residual carbon in recycled carbon fibers was determined by thermogravimetric analysis (TGA) as follows:
[0608] (i) For a sample of 1 to 4 mg obtained by crushing recycled carbon fiber, a thermogravimetric analysis was performed in a thermogravimetric analyzer for a total of about 600 minutes. The thermogravimetric analysis included the following steps: heating from room temperature to 100°C at an air supply rate of 0.2 L / min, a heating rate of 5°C / min and a recording speed of 1 / 6 second, holding at 100°C for 30 minutes, heating from 100°C to 400°C, and holding at 400°C for 480 minutes.
[0609] (ii) In the graph obtained by plotting the rate of weight loss against time, determine the inflection point of the slope, and subtract the rate of weight loss during the holding period at 100°C from the value of the rate of weight loss at that inflection point to calculate the amount of residual carbon.
[0610] The recycled carbon fiber has an average length of 5 mm.
[0611] (Contains adhesive liquid)
[0612] A binder-containing liquid was prepared with 297g of water as the dispersion medium relative to 5.05g of urethane resin as a binder.
[0613] <Granulation Process>
[0614] For granulation, a Henschel-type horizontal stirred granulator (20L Loedige mixer, manufactured by Matsubo) was used. This stirred granulator has stirring blades. The stirring blades are configured such that they are connected to a shaft mounted horizontally on the inner side wall of the container section of the stirred granulator, and rotate around this shaft. Furthermore, the stirring blades are configured with a minimum gap of approximately 2mm and a maximum gap of approximately 5mm between them and the inner wall of the container section.
[0615] The mixing granulator also has auxiliary blades to promote fiber opening.
[0616] While the stirring blades begin to rotate, 500g of the above-mentioned recycled carbon fiber and 302g of the above-mentioned binder-containing liquid are added to the container of the stirring granulator. The mixture is then mixed and granulated for 10 minutes at ambient temperature to obtain a spindle-shaped precursor.
[0617] The moisture content of the mixture is 37.0% by weight. The stirring blades rotate at 320 rpm, and the auxiliary blades rotate at 3000 rpm.
[0618] <Drying process>
[0619] The obtained precursor was dried in a dryer to obtain the carbon fiber assembly involved in Example A1.
[0620] <Carbon fiber composite>
[0621] A photograph of the carbon fiber assembly involved in Example A1 can be found here. Figure 4 and Figure 5 As can be seen in these figures, the carbon fiber assembly involved in Example A1 has a spindle-shaped shape.
[0622] (Adhesive content)
[0623] The binder content is 1.0% by weight, relative to the carbon fiber assembly of Example A1.
[0624] (Aspect Ratio)
[0625] The major and minor diameters of the carbon fiber assembly in Example A1 were measured using calipers, and the aspect ratio (major diameter / minor diameter) of the carbon fiber assembly was calculated. The minor diameter was measured at the location where the width of the carbon fiber assembly reached its maximum. The aspect ratio was 7.5 for a sample size of 50 (N=50).
[0626] (Average length, average maximum width)
[0627] When measured with calipers in a sample size of 50 (N=50), the average length of the carbon fiber assembly involved in Example A1 was 13.5 mm, and the average maximum width was 1.8 mm. Since the average length of recycled carbon fiber is 5 mm, the average length of the carbon fiber assembly is 2.7 times the average length of recycled carbon fiber.
[0628] (bulk density)
[0629] The bulk density of the carbon fiber assembly involved in Example A1 was measured. Specifically, a funnel with an outlet inner diameter of 18 mm was used to allow the sample to flow from a height of 63 mm into a 200 ml container with an inner diameter of 63 mm, filling it to the brim. Then, the weight of the sample at the shredded volume was measured. The bulk density was calculated based on this weight and the volume of the container. The result was a bulk density of 181 g / L.
[0630] <Feedability Evaluation>
[0631] The feedability of the carbon fiber assembly involved in Example A1 was evaluated. Specifically, the carbon fiber assembly involved in Example A1 was fed into a volumetric coil feeder (CFD-111, manufactured by Technovel) at a feed rate of 1 g / min, and the feedability was evaluated. In Table 1 below, cases where the feed can be sustained for 10 minutes are marked as "○".
[0632] The manufacturing conditions and evaluation results of the carbon fiber assembly involved in Example A1 are shown in Table 1 below.
[0633] Embodiment A2 of Invention 1a
[0634] Except for changes in the amount of adhesive and moisture content as shown in Table 1, the carbon fiber assembly involved in Example A2 was manufactured and evaluated in the same manner as in Example A1. The manufacturing conditions and evaluation results are shown in Table 1.
[0635] Embodiment A3 of Invention 1a
[0636] Except for changes in the amount of adhesive and moisture content as shown in Table 1, the carbon fiber assembly involved in Example A3 was manufactured and evaluated in the same manner as in Example A1. The manufacturing conditions and evaluation results are shown in Table 1.
[0637] Embodiment A4 of Invention 1a
[0638] Except that the average length of the recycled carbon fibers was set to 10 mm, the carbon fiber assembly involved in Example A4 was manufactured and evaluated in the same manner as in Example A2. The manufacturing conditions and evaluation results are shown in Table 1.
[0639] Comparative Example A1 Regarding Invention 1a
[0640] Except for setting the average length of the recycled carbon fibers to 30 mm, the same procedure as in Example A2 was followed to attempt to manufacture carbon fiber assemblies. However, the recycled carbon fibers became entangled in the pellet mill, and granular carbon fiber assemblies could not be obtained. The manufacturing conditions and results are shown in Table 1 below.
[0641] Comparative Example A2 Regarding Invention 1a
[0642] A carbon fiber assembly was manufactured in the same manner as in Example A4, except that recycled carbon fibers with a residual carbon content of 7.1% by weight were used.
[0643] Photographs of the carbon fiber assembly involved in Comparative Example A2 can be found in [the image]. Figure 6 .like Figure 6 As observed, the carbon fiber assemblies obtained in Comparative Example A2 have a flat shape, and spindle-shaped carbon fiber assemblies cannot be obtained. Most of the carbon fiber assemblies obtained in Comparative Example A2 retain the shape of the regenerated carbon fibers after cutting, and the regenerated carbon fibers are intertwined to form bundles. Furthermore, in Comparative Example A2, elliptical particles with uneven sizes were also observed. The manufacturing conditions and results are shown in Table 1 below.
[0644] [Table 1]
[0645]
[0646] Embodiment B1 of Invention 1b
[0647] <Material Modulation>
[0648] (Carbon fiber)
[0649] As the carbon fiber, recycled carbon fiber with a residual carbon content of 1.4% by weight, obtained by semiconductor thermal activation, is used.
[0650] The amount of residual carbon in recycled carbon fiber was determined by thermogravimetric analysis (TGA) as follows:
[0651] (i) For a 4 mg sample obtained by crushing recycled carbon fiber, a thermogravimetric analysis was performed in a thermogravimetric analyzer for a total of about 600 minutes. The thermogravimetric analysis included the following steps: heating from room temperature to 100°C at an air supply rate of 0.2 L / min, a heating rate of 5°C / min, and a recording speed of 1 / 6 second, holding at 100°C for 30 minutes, heating from 100°C to 400°C, and holding at 400°C for 480 minutes.
[0652] (ii) In the graph obtained by plotting the rate of weight loss against time, determine the inflection point of the slope, and subtract the rate of weight loss during the holding period at 100°C from the value of the rate of weight loss at that inflection point to calculate the amount of residual carbon.
[0653] The recycled carbon fiber has an average length of 10 mm.
[0654] (Thermoplastic resin fiber)
[0655] As a thermoplastic resin fiber, polyphenylene sulfide resin fiber (PPS resin fiber, monofilament fineness of 4.4 denier) with an average length of 5 mm is used.
[0656] (Fiber composition)
[0657] The PPS resin fiber used as the thermoplastic resin fiber in Example B1 is 70g, and the recycled carbon fiber used as the carbon fiber is 30g.
[0658] (Contains adhesive liquid)
[0659] A binder-containing liquid (water emulsion sizing agent) was prepared with 88.5g of water as the dispersion medium relative to 6.5g of urethane resin as a binder.
[0660] <Granulation Process>
[0661] For granulation, a Henschel-type horizontal stirred granulator (5L Pam Apex mixer, manufactured by Taihei Kiko Co., Ltd.) was used. This stirred granulator has stirring blades. These blades are configured such that they are connected to a shaft mounted horizontally on the inner side wall of the container section of the stirred granulator, and rotate around this shaft. Furthermore, the stirring blades are configured with a gap of approximately 2mm between them and the inner wall of the container section.
[0662] The mixing granulator also has auxiliary blades to promote fiber opening.
[0663] While the stirring blades begin to rotate, 30g of the above-mentioned recycled carbon fiber, 70g of the above-mentioned PPS resin fiber, and 95g of the above-mentioned binder-containing liquid are added to the container of the stirring granulator. The mixture is then mixed and granulated for 15 minutes at ambient temperature to obtain a spindle-shaped precursor.
[0664] The moisture content of the mixture is 45.4% by weight. The stirring blades rotate at 600 rpm, and the auxiliary blades rotate at 600 rpm.
[0665] <Drying process>
[0666] The obtained precursor was dried in a dryer to obtain the aggregate involved in Example B1.
[0667] <Collection>
[0668] The thermoplastic resin fiber and carbon fiber assembly involved in Example B1 has a spindle shape. Furthermore, the thermoplastic resin fibers and carbon fibers contained in the assembly are oriented along the long axis of the assembly.
[0669] To quantify the fiber extension direction in the assembly, the assembly was cut parallel to its long axis. For N=30 fibers randomly selected from the cross-section photographed using a digital camera, the absolute value of the fiber angle relative to the long axis of the assembly was measured. The measured values were then averaged to calculate the average fiber extension direction relative to the long axis of the assembly ("Fiber Orientation" in Table 2 below). It should be noted that fuzzy fibers (fibers partially away from the assembly) are not included in this calculation. The fiber orientation in Example B1 was 9°.
[0670] (Adhesive content)
[0671] The adhesive content of the assembly relative to Example B1 is 6.1% by weight.
[0672] (Aspect Ratio)
[0673] The aspect ratio (major diameter / minor diameter) of the assembly in Example B1 was calculated using calipers. The major diameter is the length of the assembly. The minor diameter is measured at the point where the width of the assembly is at its maximum. For a sample size of 50 (N=50), the average aspect ratio was 5.4 (average: major diameter = 20.0 mm, see below; minor diameter = 3.7 mm).
[0674] (Average length, average maximum width)
[0675] When measured with calipers in a sample size of 50 (N=50), the average length of the assembly involved in Example B1 was 20.0 mm, and the average maximum width was 3.7 mm. Since the average length of the recycled carbon fiber was 10 mm, the average length of the assembly was 2.0 times the average length of the recycled carbon fiber. Furthermore, since the average length of the PPS resin fiber was 5 mm, the average length of the assembly was 4.0 times the average length of the PPS resin fiber.
[0676] (bulk density)
[0677] The bulk density of the aggregate involved in Example B1 was measured. Specifically, using a funnel with an outlet inner diameter of 18 mm, the sample was poured from a height of 63 mm into a 200 ml container with an inner diameter of 63 mm, filling it to the brim. Then, the weight of the sample at the chopped volume was measured. The bulk density was calculated based on this weight and the volume of the container. The result was a bulk density of 164 g / L.
[0678] The manufacturing conditions and evaluation results of the assembly involved in Example B1 are shown in Table 2 below.
[0679] Embodiment B2 of Invention 1b
[0680] The following operations were performed to create the aggregate involved in Example B2.
[0681] <Material Modulation>
[0682] (Carbon fiber)
[0683] As in Example B1, recycled carbon fiber with a residual carbon content of 1.4% by weight, obtained by semiconductor thermal activation, was used as the carbon fiber. The recycled carbon fiber had an average length of 5 mm.
[0684] (Thermoplastic resin fiber)
[0685] As a thermoplastic resin fiber, polyphenylene sulfide resin fiber (PPS resin fiber, monofilament fineness 4.4 denier) with an average length of 5 mm is used.
[0686] (Fiber composition)
[0687] The thermoplastic resin fiber used in Example B2 is 350g of PPS resin fiber and the recycled carbon fiber used as carbon fiber is 150g.
[0688] (Contains adhesive liquid)
[0689] A binder-containing liquid (water emulsion sizing agent) was prepared with 256g of water as the dispersion medium relative to 21.0g of urethane resin as the binder.
[0690] <Granulation Process>
[0691] For granulation, a horizontal mixing granulator (30L MTI mixer, manufactured by Tsukishima Machinery Co., Ltd.) was used.
[0692] The mixing granulator has mixing blades and auxiliary blades for fiber opening.
[0693] While the stirring blades begin to rotate, 150g of the above-mentioned recycled carbon fiber, 350g of the above-mentioned PPS resin fiber, and 277g of the above-mentioned binder-containing liquid are added to the container of the stirring granulator. The mixture is then mixed and granulated for 15 minutes at ambient temperature to obtain a spindle-shaped precursor.
[0694] The moisture content of the mixture is 32.9% by weight. The stirring blades rotate at 235 rpm, and the auxiliary blades rotate at 3,000 rpm.
[0695] <Drying process>
[0696] The obtained precursor was dried in a dryer to obtain the aggregate involved in Example B2.
[0697] <Collection>
[0698] Figure 7 and Figure 8 These are photographs of the assembly involved in Example B2. As can be seen in these figures, the assembly of thermoplastic resin fibers and carbon fibers involved in Example B2 has a spindle-shaped form. Furthermore, the thermoplastic resin fibers and carbon fibers contained in the assembly are oriented along the long axis of the assembly. Similar to Example B1, the fiber orientation degree for Example B2 was calculated, and the result is 7°.
[0699] (Adhesive content)
[0700] The adhesive content of the assembly relative to Example B2 is 4.0% by weight.
[0701] (Aspect Ratio)
[0702] The aspect ratio (major diameter / minor diameter) of the assembly in Example B2 was calculated using calipers. The major diameter is the length of the assembly. The minor diameter was measured at the point where the width of the assembly is at its maximum. The average aspect ratio for a sample size of 50 (N=50) was 6.7 (average: major diameter = 17.4 mm, see below; minor diameter = 2.6 mm).
[0703] (Average length, average maximum width)
[0704] When measured using calipers with a sample size of 50 (N=50), the average length of the aggregate involved in Example B2 was 17.4 mm, and the average maximum width was 2.6 mm. Since the average length of the recycled carbon fiber was 5 mm, the average length of the aggregate was 3.5 times the average length of the recycled carbon fiber. Furthermore, since the average length of the PPS resin fiber was 5 mm, the average length of the aggregate was 3.5 times the average length of the PPS resin fiber.
[0705] (bulk density)
[0706] The bulk density of the aggregate involved in Example B2 was measured in the same manner as in Example B1. The result was a bulk density of 189 g / L.
[0707] The manufacturing conditions and evaluation results of the assembly involved in Example B2 are shown in Table 2 below.
[0708] Comparative Example B1 Regarding Invention 1b
[0709] Except for using polyphenylene sulfide resin powder (PPS powder, median diameter 270 μm) instead of PPS resin fibers, the same procedure as in Example B2 above was followed when attempting to manufacture an aggregate, but a spindle-shaped aggregate could not be obtained.
[0710] Figure 9 This is a photograph showing the material obtained as a result of Comparative Example B1. The material obtained in Comparative Example B1 mainly consists of carbon fiber aggregates and PPS powder with inconsistent shapes and sizes, which exist separately from each other. Since the material involved in Comparative Example B1 does not become a dispersed mixture of PPS resin and carbon fiber, granulation is required through a mixing process in order to manufacture carbon fiber-containing molded articles using the material involved in Comparative Example B1.
[0711] [Table 2]
[0712]
[0713] Embodiment C1 of Invention 2
[0714] <Material Modulation>
[0715] (Recycled carbon fiber)
[0716] As recycled carbon fiber, recycled carbon fiber with an average length of 5 mm, an average single fiber diameter of 7.0 μm, a single fiber tensile strength of 4.2 GPa, a Weibull shape factor of 8.7, and a residual carbon content of 0.3% by weight is generated by semiconductor thermal activation method using CFRP that has been cut as raw material and according to the method disclosed in Invention 2 of this invention.
[0717] (Single fiber tensile strength)
[0718] According to JIS R7606, the tensile strength of a single fiber is measured as follows:
[0719] At least 30 individual fibers were collected from the fiber bundle.
[0720] The diameter of a single fiber is measured from a side image of the fiber taken using a digital microscope, and the cross-sectional area is calculated.
[0721] The sampled monofibers were fixed onto the perforated backing paper using an adhesive.
[0722] A paper insert with a fixed single fiber is mounted on a tensile testing machine. A tensile test is performed with a specimen length of 10 mm and a strain rate of 1 mm / min. The tensile breaking stress is then determined.
[0723] The tensile strength is calculated from the cross-sectional area of a single fiber and the tensile fracture stress.
[0724] The average tensile strength of at least 30 individual fibers is taken as the tensile strength of a single fiber.
[0725] (Weibull shape coefficient)
[0726] The Weibull shape factor is calculated according to the following formula:
[0727] lnln{1 / (1-F)}=m×lnσ+C
[0728] (In the formula, F is the failure probability obtained by the cumulative distribution method of symmetrical samples, σ is the tensile strength of a single fiber (MPa), m is the Weibull shape coefficient, and C is a constant.)
[0729] We can perform a Weibull plot using lnln{1 / (1-F)} and lnσ, and then determine the Weibull shape coefficient m from the first-order approximate slope.
[0730] (Residual carbon content)
[0731] The amount of residual carbon in recycled carbon fiber is determined by thermogravimetric analysis (TGA) as follows:
[0732] (i) For a 4 mg sample obtained by crushing recycled carbon fiber, a thermogravimetric analysis was performed in a thermogravimetric analyzer for a total of about 600 minutes. The thermogravimetric analysis included the following steps: heating from room temperature to 100°C at an air supply rate of 0.2 L / min, a heating rate of 5°C / min, and a recording speed of 1 / 6 second, holding at 100°C for 30 minutes, heating from 100°C to 400°C, and holding at 400°C for 480 minutes.
[0733] (ii) In the graph obtained by plotting the rate of weight loss against time, determine the inflection point of the slope, and subtract the rate of weight loss during the holding period at 100°C from the value of the rate of weight loss at that inflection point to calculate the amount of residual carbon.
[0734] According to the method of this invention, a spindle-shaped carbon fiber assembly was obtained from the aforementioned recycled carbon fiber. Specifically, after the recycled carbon fiber was defibrated using a mixer, it was mixed with an aqueous dispersion of an epoxy resin as a binder using a stirred granulator. The resulting spindle-shaped precursor was then dried in a dryer to obtain a spindle-shaped carbon fiber assembly. It should be noted that 2% by weight of epoxy resin was imparted to the recycled carbon fiber.
[0735] When the obtained spindle-shaped carbon fiber assembly was measured in the same manner as in Embodiment A1 of Invention 1a, the average length of the assembly was 10.8 mm, the average maximum width of the assembly was 1.4 mm, and the bulk density of the assembly was 132 g / L. Furthermore, the aspect ratio of the assembly was 7.7.
[0736] (Thermoplastic resin)
[0737] As the base thermoplastic resin, polycarbonate resin (L1225WP, manufactured by Teijin Corporation: molecular weight 218,000) is used.
[0738] Manufacturing of carbon fiber reinforced thermoplastic resin particles
[0739] The aforementioned polycarbonate, which serves as a thermoplastic resin, is fed into a twin-screw compounding extruder. The resulting recycled carbon fiber aggregate is fed from a side feeder and dispersed in the polycarbonate resin, which serves as the parent material, for granulation, thereby obtaining the carbon fiber reinforced thermoplastic resin particles described in Example C1.
[0740] The weights of the thermoplastic resin and recycled carbon fiber fed into the extruder were measured, and the fiber weight ratio (wt%) of the particles involved in Example C1 was calculated as ((recycled carbon fiber (g) / (recycled carbon fiber (g) + thermoplastic resin (g)))×100).
[0741] Using an injection molding machine (Toshiba Machine Manufacturing, 130T injection molding machine, cylinder temperature 300°C, mold temperature 100°C), the obtained granules are molded into dumbbell plates with a length of 170mm × width of 10mm × thickness of 4mm (the molded product involved in Example C1).
[0742] The tensile strength, flexural strength, and flexural modulus of the obtained dumbbell plates were 99 MPa, 142 MPa, and 7.2 GPa, respectively. The tensile strength, flexural strength, and flexural modulus were determined using the following procedures.
[0743] (Tensile strength)
[0744] Using the above-mentioned dumbbell plates, the tensile strength was determined according to ISO 527.
[0745] (Flexural strength)
[0746] Using the dumbbell plates described above, the flexural strength was determined according to ISO 178.
[0747] (Flexural modulus)
[0748] Using the dumbbell plates described above, the flexural modulus of elasticity was determined according to ISO 178.
[0749] It should be noted that the residual average fiber length of the recycled carbon fibers in the particles is 348 μm, and the frequency of single fibers below 300 μm is 36%. Their measurement methods are described below.
[0750] (Residual average fiber length)
[0751] Regarding the average fiber length (residual average fiber length) of recycled carbon fibers in carbon fiber reinforced thermoplastic resin granules, the matrix resin in the granules was removed by sulfuric acid decomposition. After filtration, the fiber length of more than 300 individual fibers was measured using a microscope and calculated as a numerical average.
[0752] (Frequency of occurrence of single fibers below 300μm)
[0753] The frequency of single fibers below 300μm is determined by operating in the same manner as the above-mentioned average fiber length determination, measuring the fiber length of single fibers, and then calculating the proportion of single fibers below 300μm.
[0754] The results of Example C1 are shown in Table 3 below.
[0755] Comparative Example C1 of Invention 2
[0756] In Comparative Example C1, recycled carbon fibers with a residual carbon content of 7.1% by weight were used, obtained by a conventional thermal decomposition method without the use of semiconductors. It should be noted that because the residual carbon content was more than 5% by weight, the tensile strength of a single fiber and the Weibull shape factor could not be determined.
[0757] In Comparative Example C1, no mixer treatment or carbon fiber assembly manufacturing was performed. Instead, recycled carbon fiber, as short (chopped) recycled carbon fiber, was fed to a twin-screw extruder. Otherwise, the same procedures as in Example C1 were followed for the manufacturing and evaluation of pellets and dumbbell-shaped sheets. The results are shown in Table 3 below. It should be noted that the carbon fiber regenerated by the existing pyrolysis method (the short recycled carbon fiber involved in Comparative Example C1) was bundled with residual carbides and could therefore be fed to the twin-screw compounding extruder from the side feeder.
[0758] Comparative Example C2 of Invention 2
[0759] In Comparative Example C2, except that short fibers of commercially available virgin carbon fiber (HT C422, manufactured by Teijin Corporation) were used instead of recycled carbon fiber, the same procedure as in Example C1 was followed for the manufacture and evaluation of the pellets and dumbbell plates.
[0760] The results are shown in Table 3 below. It should be noted that the physical properties of the virgin carbon fiber involved in Comparative Example C2 are shown in Table 3 below.
[0761] The molded article of Example C1 exhibits superior mechanical properties compared to the molded article of Comparative Example C1. This is not intended to be theoretically limited; for example, the recycled carbon fiber of Example C1 has less residual carbon and better adhesion to the resin compared to the recycled carbon fiber of Comparative Example C1.
[0762] Furthermore, although the molded article of Example C1 contains recycled carbon fiber, it exhibits mechanical properties equivalent to those of the molded article of Comparative Example C2. In Example C1, the frequency of single fibers pulverized to below 300 μm is 36%, which is lower than the 55% in Comparative Example C2. Therefore, in Example C1, a higher mechanical property enhancement effect can be obtained, and although recycled carbon fiber with low single fiber tensile strength is used, it is considered to exhibit mechanical properties equivalent to those of Comparative Example C2, which uses virgin carbon fiber. It should be noted that this is not intended to be theoretically limited. As a reason for the lower frequency of single fibers pulverized to below 300 μm in Example C1, the following can be cited: since the recycled carbon fiber used in Example C1 is a fiber regenerated by semiconductor thermal activation, the deviation in single filament tensile strength is smaller compared to Comparative Example C2, and the Weibull shape factor is higher (8.7).
[0763] [Table 3]
[0764]
[0765] Reference Examples 1-3 and Reference Comparative Example 1
[0766] In Reference Examples 1-3 and Reference Comparative Example 1, carbon fiber reinforced plastic (CFRP) sheets, which are plastic-containing materials, were subjected to heat treatment to evaluate the plastic decomposition efficiency.
[0767] <Reference Example 1>
[0768] The procedure is as follows, referring to Example 1.
[0769] (Providing and configuring materials)
[0770] As a semiconductor material, chromium oxide (Cr2O3, purity ≥ 99%, manufactured by Gensei Chemicals) is applied to the surface of a carrier with a honeycomb structure. The carrier with the honeycomb structure has 13 cells / 25 mm.
[0771] As a plastic material, CFRP sheets containing 41% by weight of epoxy resin are used.
[0772] The furnace has an internal volume of 9L. Inside the furnace, CFRP plates are mounted on a carrier supporting chromium oxide, which serves as a semiconductor material. The carrier and the CFRP plates are in contact with each other.
[0773] The surface temperature of the CFRP plate is measured by a sensor positioned within 5 mm of the surface of the CFRP plate.
[0774] (Heat treatment)
[0775] The internal temperature of the heating furnace is controlled by the output power of the heater, thereby increasing the internal temperature of the heating furnace.
[0776] Before the surface temperature of the CFRP plate reaches 300°C, a mixture of air and nitrogen with an oxygen concentration of 6% by volume is introduced into the heating furnace. This mixture is introduced by drawing gas at a rate of 70 L / min from an intake port located at the top of the furnace, causing the mixture to flow into a gas supply port located at the bottom of the furnace. The oxygen concentration within the furnace is measured using an oxygen monitor.
[0777] The CFRP plate was heated for 30 minutes in an environment where the oxygen concentration was controlled at 6% by volume by introducing the aforementioned mixed gas. During the heating process, the heater output power of the heating furnace was adjusted to raise the surface temperature of the CFRP plate to a first surface temperature of 376°C.
[0778] (evaluate)
[0779] The evaluation of the plastic decomposition efficiency in the method described in Example 1 was performed by calculating the weight reduction rate (wt%) from the difference between the weight of the CFRP sheet before heat treatment and the weight of the CFRP sheet after heat treatment. The results are shown in Table 4.
[0780] <Reference Example 2>
[0781] Inside the heating furnace, the carrier and the CFRP plate were arranged with a 30mm gap between them, and the surface temperature of the CFRP plate was raised to 377°C during the heat treatment. Otherwise, the heat treatment and evaluation of Reference Example 2 were performed in the same manner as in Reference Example 1. The results are shown in Table 4.
[0782] <Reference Example 3>
[0783] Except that the heat treatment time was set to 60 minutes and the surface temperature of the CFRP plate was raised to 371°C during the heat treatment, the heat treatment and evaluation of Reference Example 3 were performed in the same manner as in Reference Example 1. The results are shown in Table 4.
[0784] <Comparative Example 1 for Reference>
[0785] Except for the use of semiconductor materials and raising the surface temperature of the CFRP plate to 370°C during the heat treatment, the heat treatment and evaluation of Comparative Example 1 were performed in the same manner as in Reference Example 1. The results are shown in Table 4.
[0786] [Table 4]
[0787] Table 4
[0788]
[0789] As shown in Table 4, in the presence of semiconductor materials, under the condition of introducing a low oxygen concentration gas with an oxygen concentration of 6% by volume, in Reference Examples 1 to 3, when heated to a surface temperature of 371°C to 377°C, the decomposition efficiency of the plastic material was higher than that of Reference Comparative Example 1, which did not use semiconductor materials.
[0790] It should be noted that in Reference Example 3, although the processing time was extended to 60 minutes, the increase in weight reduction rate compared to Reference Example 1, where the processing time was 30 minutes, was limited. This is believed to be because the sample surface was covered with carbides during the heat treatment, resulting in a decrease in decomposition efficiency.
[0791] Reference Example 4 and Reference Comparative Example 2
[0792] <Reference Example 4>
[0793] Except for heating at a surface temperature of 500°C for 60 minutes, the treatment and evaluation involved in Reference Example 4 were performed in the same manner as in Reference Example 1. The results are shown in Table 5 below.
[0794] <Comparative Example 2>
[0795] Except for the absence of semiconductor materials, the same procedures and evaluations as those in Reference Example 2 were performed as in Reference Example 4. The results are shown in Table 5 below.
[0796] [Table 5]
[0797] Table 5
[0798]
[0799] Photographs of the samples after the treatments described in Reference Example 4 and Reference Comparative Example 2 are shown below. Figure 11 and Figure 12 Additionally, a photograph of the sample before processing can be found here. Figure 10 .
[0800] As can be seen in Table 5, in Reference Example 4, which was subjected to heat treatment with a semiconductor material under a low oxygen concentration gas of 6% by volume, a higher plastic decomposition efficiency was observed compared to Reference Comparative Example 2, which was subjected to heat treatment without a semiconductor material under a low oxygen concentration gas of 6% by volume.
[0801] Additionally, as in Figure 12 As seen in the above, blocky residual carbon from the plastic adhered to the surface of the treated sample involved in Comparative Example 2. On the other hand, as in Figure 11 As observed, no residual carbon adhesion was confirmed in the treated sample described in Reference Example 4. Figure 10 The surface of the untreated sample shown also has a relatively smooth and highly uniform surface.
[0802] Reference Examples 5-9
[0803] In Reference Examples 5-9, a two-stage heat treatment was performed on a CFRP sheet or pressure vessel containing plastic material. The decomposition efficiency was then evaluated, and the physical properties of the carbon fibers (carbon fiber material) obtained through the heat treatment were assessed.
[0804] <Reference Example 5>
[0805] The following steps are performed with reference to Example 5.
[0806] (Providing and configuring materials)
[0807] As a semiconductor material, a material with chromium oxide (Cr2O3, purity ≥ 99%, manufactured by a pure chemical company) applied to the surface of the carrier with a honeycomb structure is used. The carrier with a honeycomb structure has 13 compartments / 25mm.
[0808] As a plastic material, a CFRP sheet containing 41% by weight of epoxy resin was used. The physical properties of the carbon fibers contained in the CFRP sheet before treatment are shown in Table 6 as Reference Example 1.
[0809] The internal volume of the heating furnace is 0.0525 m³. 3 Inside the heating furnace, CFRP plates are mounted on a carrier containing chromium oxide, a semiconductor material. The carrier and the CFRP plates are in contact with each other.
[0810] The surface temperature of the CFRP board is measured by a sensor positioned 5 mm from the surface of the CFRP board.
[0811] (Heat treatment)
[0812] The internal temperature of the heating furnace is controlled by the output power of the heater, causing the internal temperature of the heating furnace to rise. Then, before the surface temperature of the CFRP plate reaches 300°C, a mixture of air and nitrogen with an oxygen concentration of 8% by volume is introduced into the heating furnace. The mixture is introduced into the heating furnace by suction at a gas introduction rate of 190 L / min, and then the mixture flows into the gas supply section located in the heating furnace.
[0813] It should be noted that in Reference Example 5, and in Reference Example 6 and Reference Comparative Example 4 described below, the oxygen concentration inside the heating furnace was measured using an oxygen monitor installed inside the furnace. Regarding Reference Examples 7-9, the oxygen concentration inside the furnace was calculated based on the furnace volume and the gas introduction rate.
[0814] The generation of decomposition gases was confirmed at the time point when the surface temperature of the CFRP plate reached 300°C.
[0815] The CFRP plate was heated for 120 minutes in an environment where the oxygen concentration was controlled at 8% by volume by introducing the aforementioned mixed gas. During the heating process, the heater output power of the heating furnace was adjusted to raise the surface temperature of the CFRP plate to a first surface temperature of 450°C.
[0816] (Secondary heat treatment)
[0817] Then, with the gas suction pressure maintained constant, the nitrogen supply was stopped, and only air was supplied. The oxygen concentration inside the furnace was confirmed to be above 10% by volume before further heating. During the 260-minute heating process, the surface temperature of the CFRP plate was raised to 500°C. It should be noted that the average oxygen concentration over 260 minutes was 14% by volume, and the maximum oxygen concentration was 18% by volume.
[0818] In Reference Example 5, 0.8 kg of CFRP sheet was processed. The processing rate relative to the furnace volume was 15.2 kg / m². 3 .
[0819] (Residual carbon content)
[0820] The residual carbon content from plastic in the recycled carbon fibers (regenerated carbon fibers) recovered after heat treatment was determined by thermogravimetric analysis. The residual carbon content values in Table 6 below represent the amount of residual carbon relative to the carbon fiber (wt%).
[0821] Thermogravimetric analysis is performed as follows:
[0822] (i) For sample pieces of 1 to 4 mg obtained by crushing the recycled carbon fiber, thermogravimetric analysis was performed in a thermogravimetric analyzer for a total of 300 minutes, the thermogravimetric analysis having the following steps: heating from room temperature to 100°C at an air supply rate of 0.2 L / min, a heating rate of 5°C / min and a recording speed of 1 / 6 second, holding at 100°C for 30 minutes, heating from 100°C to 400°C, and holding at 400°C;
[0823] (ii) In the graph of weight loss rate versus time, determine the inflection point of the slope, and subtract the weight loss rate during the holding period at 100°C from the weight loss rate value at that inflection point to calculate the amount of residual carbon.
[0824] In addition, for the carbon fibers recovered after heat treatment, the diameter of the single filament and the tensile strength of the single fiber are measured, and the Weibull shape factor is calculated.
[0825] (Single fiber tensile strength)
[0826] The tensile strength of a single fiber is measured according to JIS R7606, as follows:
[0827] At least 30 individual fibers were collected from the fiber bundle.
[0828] The diameter of a single fiber is measured from a side image of the fiber taken using a digital microscope, and the cross-sectional area is calculated.
[0829] The sampled monofibers were fixed onto the perforated backing paper using an adhesive.
[0830] A paper insert with a fixed single fiber is mounted on a tensile testing machine. A tensile test is performed with a specimen length of 10 mm and a strain rate of 1 mm / min. The tensile breaking stress is then determined.
[0831] The tensile strength is calculated from the cross-sectional area of a single fiber and the tensile fracture stress.
[0832] The average tensile strength of at least 30 individual fibers is taken as the tensile strength of a single fiber.
[0833] (Weibull shape coefficient)
[0834] The Weibull shape factor is calculated according to the following formula:
[0835] lnln{1 / (1-F)}=m×lnσ+C
[0836] (In the formula, F is the failure probability obtained by the cumulative distribution method of symmetrical samples, σ is the tensile strength of a single fiber (MPa), m is the Weibull shape coefficient, and C is a constant.)
[0837] We perform Weibull plots using lnln{1 / (1-F)} and lnσ, and obtain the Weibull shape coefficient m using the efficiency of a first-order approximation.
[0838] The evaluation results are shown in Table 6. It should be noted that the fiber monofilament diameter is the average diameter of the monofilaments obtained by measuring at least 30 monofilaments as described above.
[0839] <Reference Example 6>
[0840] The process was performed using a pressure vessel containing plastic material, drawing in a mixed gas at a gas introduction rate of 127 L / min, and setting the oxygen concentration, surface temperature, and heating treatment time as shown in Table 6 below. Otherwise, the process was carried out in the same manner as in Reference Example 5.
[0841] The pressure vessel treated in Reference Example 6 has an aluminum liner and 44% by weight of FRP (fiber-reinforced plastic), which contains 31% by weight of reinforcing fibers and 13% by weight of epoxy resin. The reinforcing fibers are mainly composed of carbon fibers, with a small amount of glass fibers. The pressure vessel has a capacity of 2.0L.
[0842] The amount of FRP processed in Example 6 was 0.47 kg. The processing rate relative to the furnace volume was 9.0 kg / m³. 3 .
[0843] The evaluation results of the plastic decomposition efficiency and the physical property evaluation results of the recovered carbon fiber related to Reference Example 6 are shown in Table 4. It should be noted that after a secondary heat treatment of 180 minutes, the average oxygen concentration was 18% by volume and the maximum oxygen concentration was 20% by volume.
[0844] It should be noted that the physical properties of the carbon fibers contained in the pressure vessel before treatment are shown in Table 6 as reference example 2.
[0845] <Reference Example 7>
[0846] The internal volume of the heating furnace is 0.1435 m³. 3 A mixture of superheated steam and air was introduced into the heating furnace at a gas introduction rate of 29 L / min, and the surface temperature and heating time were set as shown in Table 6 below. Otherwise, the heating process was carried out in the same manner as in Reference Example 5.
[0847] It should be noted that the internal temperature of the heating furnace and the surface temperature of the sample are controlled by the output power of the heater and the temperature of the superheated steam.
[0848] In Reference Example 7, 1.0 kg of CFRP sheet was processed. The processing rate relative to the furnace volume was 7.0 kg / m³. 3 .
[0849] The evaluation results of the plastic decomposition efficiency and the physical property evaluation results of the recovered carbon fiber related to Reference Example 7 are shown in Table 6. It should be noted that in the secondary heating treatment, only air was forced into the furnace at a rate of 29 L / min.
[0850] <Reference Example 8>
[0851] Except for using a pressure vessel as the plastic material and setting the surface temperature and heat treatment time as shown in Table 6 below, the process was carried out in the same manner as in Reference Example 7.
[0852] The pressure vessel used in Reference Embodiment 8 is the same as the pressure vessel used in Reference Embodiment 6.
[0853] The amount of FRP processed in Example 8 was 0.47 kg. The processing rate relative to the furnace internal volume was 3.3 kg / m². 3 .
[0854] The evaluation results of the plastic decomposition efficiency and the physical property evaluation results of the recovered carbon fiber related to Reference Example 8 are shown in Table 6. It should be noted that in the secondary heating treatment, only air was forced into the furnace at a rate of 29 L / min.
[0855] <Reference Example 9>
[0856] The internal volume of the heating furnace is 0.049 m³. 3 A mixture of superheated steam and air is introduced into the heating furnace at a gas introduction rate of 25 L / min. The surface temperature and heating time are set as shown in Table 6 below. Otherwise, the process is carried out in the same manner as in Reference Example 7.
[0857] In Reference Example 9, a CFRP board with an epoxy resin ratio of 38% was treated. The processing rate was 1.6 kg / m² relative to the furnace volume. 3 .
[0858] The evaluation results of the plastic decomposition efficiency and the physical property evaluation results of the recovered carbon fiber related to Reference Example 9 are shown in Table 6. It should be noted that during the secondary heating treatment, while continuing to supply superheated steam, the air volume was increased, and a gas with an oxygen concentration of 11% by volume was forced into the furnace at a rate of 38 L / min.
[0859] The physical properties of the carbon fibers contained in the CFRP plate described in Reference Example 9 before processing are used as Reference Example 3, as shown in Table 6.
[0860] Reference Comparative Example 3
[0861] In Comparative Example 3, the supply and configuration of materials were carried out in the same manner as in Comparative Example 5. Instead of adjusting the oxygen concentration in the furnace environment, the internal temperature of the furnace was increased.
[0862] As a result, with the heater output power remaining constant at the point when the CFRP plate surface temperature reached 300°C, excess self-heating occurred, causing the CFRP plate surface temperature to rise to 485°C. The results are recorded in Table 6.
[0863] In Comparative Example 3, 0.8 kg of CFRP sheet was processed. The processing rate relative to the furnace volume was 15.2 kg / m². 3 .
[0864] Reference Comparative Example 4
[0865] Except that no semiconductor material was used, the process was carried out in the same manner as in Reference Example 6.
[0866] The amount of FRP processed in Comparative Example 4 was 0.47 kg. The processing rate relative to the furnace internal volume was 9.0 kg / m³. 3 .
[0867] Regarding Comparative Example 4, the physical property evaluation results of the recovered carbon fibers are shown in Table 6. After a secondary heat treatment of 180 minutes, the average oxygen concentration was 18% by volume and the maximum oxygen concentration was 20% by volume.
[0868] [Table 6]
[0869]
[0870] As shown in Table 6, Reference Examples 5-9, which involved introducing a low-oxygen-concentration gas with an oxygen concentration of 6-8% by volume, undergoing one heating treatment in the presence of a semiconductor material, and then undergoing two further heating treatments at an increased oxygen concentration, exhibited low residual carbon content (residual carbon content) and demonstrated very excellent plastic decomposition efficiency.
[0871] Furthermore, in Comparative Example 3, where oxygen concentration was not controlled, excessive self-heating occurred. In contrast, in Comparative Examples 5-9, where a low-oxygen-concentration gas of 6-8% by volume was introduced into the furnace, no excessive self-heating was observed. In Comparative Example 3, because the decomposition process began without prior reduction of the oxygen concentration, an excess of oxygen was generated. As a result, it was considered impossible to properly control the decomposition temperature in the presence of the semiconductor material.
[0872] Furthermore, compared to the carbon fibers before treatment (Reference Examples 1 to 3), the recovered carbon fibers in Examples 5 to 9 maintained the same fiber filament diameter and tensile strength, and the Weibull shape factor of the tensile strength of the single fibers increased. In other words, in Examples 5 to 9, carbon fibers with superior physical properties compared to the carbon fibers before manufacturing carbon fiber reinforced plastics were recovered.
[0873] Moreover, the carbon fibers recovered in Reference Example 6, which were subjected to heat treatment with semiconductor materials, exhibit superior quality, particularly in terms of single fiber tensile strength and Weibull shape factor, compared to the carbon fiber materials recovered in Reference Comparative Example 4, which were subjected to heat treatment without semiconductor materials.
[0874] Symbol Explanation
[0875] 100: Mixing granulator;
[0876] 120: Container Department;
[0877] 140: Agitator blades;
[0878] 160: Shaft portion;
[0879] A: Direction of rotation;
[0880] C: gap;
[0881] 11: Semiconductor materials;
[0882] 12: Contains plastic materials;
[0883] 20: Heating furnace;
[0884] 21: A carrier containing semiconductor materials;
[0885] 22: Contains plastic materials;
[0886] 23: Heat source (heater);
[0887] 24: Gas Supply Department;
[0888] 25: Exhaust port;
[0889] 26: The internal space of the heating furnace;
[0890] 27: Temperature sensor.
Claims
1. A method for manufacturing a spindle-shaped assembly, the method comprising: Provide a mixture consisting of at least carbon fiber and a binder liquid; A spindle-shaped precursor is produced by rotating the above mixture in a container; as well as Dry the above-mentioned precursor, The carbon fiber mentioned above is recycled carbon fiber. The aforementioned recycled carbon fiber contains residual carbon components, and the content of these residual carbon components is greater than 0% by weight and less than 5.0% by weight, relative to the aforementioned recycled carbon fiber. The average length of the aforementioned recycled carbon fibers is greater than 1 mm and less than 30 mm, and The recycled carbon fibers contained in the aforementioned spindle-shaped carbon fiber assembly are oriented along the long axis of the aforementioned spindle-shaped carbon fiber assembly.
2. The method for manufacturing the spindle-shaped assembly according to claim 1, wherein, The aforementioned spindle-shaped assembly is a spindle-shaped carbon fiber assembly. The manufacturing method is characterized by comprising: manufacturing a spindle-shaped precursor by rotating the mixture in a container within a gap between the inner wall of the container and a rotating body inside the container.
3. The method of claim 2, wherein, The average length of the aforementioned carbon fiber assemblies ranges from 1.5 mm to 60 mm.
4. The method of claim 2 or 3, wherein, The amount of the adhesive-containing liquid in the mixture is 20% to 60% by weight relative to the mixture described above.
5. The method of claim 2 or 3, wherein, The amount of adhesive contained in the above-mentioned adhesive-containing liquid is 0.1% to 10% by weight, relative to the above-mentioned recycled carbon fiber.
6. The method of claim 2 or 3, wherein, The average length of the aforementioned carbon fiber assembly is 1.2 to 4.0 times the average length of the recycled carbon fibers contained in the aforementioned carbon fiber assembly.
7. The method for manufacturing the spindle-shaped assembly according to claim 1, wherein, The aforementioned spindle-shaped assembly is a spindle-shaped assembly of thermoplastic resin fibers and carbon fibers. The mixture also contains thermoplastic resin fibers.
8. The method of claim 7, wherein, The above mixture is rotated in a container, within the gap between the inner wall of the container and the rotating body inside the container, to produce the above spindle-shaped precursor.
9. The method of claim 2 or 3, comprising: The aforementioned recycled carbon fiber is manufactured by decomposing the plastic components contained in carbon fiber-containing plastic products using a semiconductor thermal activation method.
10. A spindle-shaped assembly comprising carbon fibers and a binder. The carbon fiber mentioned above is recycled carbon fiber. The aforementioned recycled carbon fiber contains residual carbon components, and the content of these residual carbon components is greater than 0% by weight and less than 5.0% by weight, relative to the aforementioned recycled carbon fiber. The average length of the aforementioned recycled carbon fibers is greater than 1 mm and less than 30 mm, and The recycled carbon fibers contained in the aforementioned spindle-shaped carbon fiber assembly are oriented along the long axis of the aforementioned spindle-shaped carbon fiber assembly.
11. The spindle-shaped assembly according to claim 10, characterized in that: The aforementioned spindle-shaped assembly is a spindle-shaped carbon fiber assembly composed of at least recycled carbon fibers and an adhesive, wherein, The average length of the aforementioned carbon fiber assemblies ranges from 1.5 mm to 60 mm.
12. The assembly of claim 11, wherein, The average length of the spindle-shaped carbon fiber assembly along its major axis is 1.2 to 4.0 times the average length of the recycled carbon fibers contained in the spindle-shaped carbon fiber assembly.
13. The spindle-shaped assembly of claim 10, which is a spindle-shaped assembly of thermoplastic resin fibers and carbon fibers, comprising recycled carbon fibers, thermoplastic resin fibers, and an adhesive. The recycled carbon fibers and thermoplastic resin fibers contained in the above-mentioned assembly are oriented along the long axis of the above-mentioned assembly.
14. The assembly of claim 13, wherein, The average length of the above-mentioned aggregates is 1.5mm to 60mm.
15. The assembly according to claim 13 or 14, wherein, The average lengths of the aforementioned carbon fiber and the aforementioned thermoplastic resin fiber are respectively 1 mm or more and less than 30 mm.
16. The assembly according to claim 13 or 14, wherein, The average length of the above-mentioned assembly is 1.2 to 5.0 times the average length of the carbon fibers and the average length of the thermoplastic resin fibers contained in the above-mentioned assembly.
17. The assembly according to claim 10 or 11, wherein, The content of the adhesive is 0.1% to 10% by weight relative to the spindle-shaped assembly.
18. The assembly according to claim 13 or 14, wherein, The aforementioned thermoplastic resin fibers are selected from polyolefin resin fibers, polyester resin fibers, polyamide resin fibers, polyetherketone resin fibers, polycarbonate resin fibers, phenoxy resin fibers, and polyphenylene sulfide resin fibers, as well as mixtures thereof.
19. A method for manufacturing carbon fiber reinforced thermoplastic resin particles, comprising: Provide recycled carbon fiber; Thermoplastic resins are available; as well as The above-mentioned recycled carbon fiber and the above-mentioned molten thermoplastic resin are mixed together. Among them, the aforementioned recycled carbon fiber has a single fiber tensile strength of over 3.0 GPa and a Weibull shape factor of over 6.0, and The aforementioned recycled carbon fiber contains residual carbon components, and the content of residual carbon components is greater than 0% by weight and less than 5.0% by weight, relative to the aforementioned recycled carbon fiber. The aforementioned recycled carbon fiber is provided using the spindle-shaped carbon fiber assembly as described in claim 10.
Citation Information
Patent Citations
Method for producing composite intermediate material
JP2019155634A
Treatment method and treatment device of laminated chip-shaped or tabular plastic composite material
JP2019189674A
Method for manufacturing composite which contains recycle carbon fiber
JP2020049820A
Carbon fiber aggregate and method for producing the same
JP2020180421A
Carbon fiber assembly
JP2020196882A